Hollow spherical particles
By using lignin-sugar complex to construct hollow spherical particles, the problems of biocompatibility and environmental friendliness in the prior art are solved, and high-function and high value-added hollow spherical particles are realized, with a variety of excellent properties.
Patent Information
- Application Number
- CN202380045432.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-06-08
- Publication Date
- 2025-02-07
AI Technical Summary
Existing hollow spherical particles have problems in biocompatibility, agent inclusion, cell permeability/reachability, surface charge control, sustained release, manufacturing cost and structural stability, and petroleum-derived capsule raw materials are difficult to recover, making it a Environmental microplastics.
The lignin-sugar complex is used as a self-assembly of hollow spherical particles, and the formation of α ether bonds, α ester bonds and γ ester bonds is used to construct high-function and high-value-added hollow spherical particles.
The hollow spherical particles with biocompatible, biodegradability and non-toxicity are achieved, with sustained release, positive and negative surface charges, cell permeability/reachability, stability, light resistance and selective recognition.
Smart Images

Figure CN119403546A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to hollow spherical particles and the like. Background Art
[0002] Hollow spherical particles such as microcapsules and nanocapsules are widely used in the fields of pesticides, detergents, softeners, fragrances, cosmetics, pharmaceuticals, latent heat storage materials (PCM), fibers, coatings, adhesives, etc. By encapsulating molecules such as drugs in particles, it is expected that the drugs can act at the appropriate time in space and time; the drugs can be protected and dispersed or aggregated appropriately; the objects can be protected and weather-resistant by coating, etc. The above capsules are widely used worldwide, but the capsule raw materials from petroleum are difficult to recover after being released into the environment, and become the source of microplastics in soil, rivers, and oceans. The development of raw materials with low environmental burden from natural sources has become a technical problem. Liposomes, polymer micelles, metal particles, etc. are used in drug carriers (so-called drug delivery systems: DDS) in the pharmaceutical field, but there are problems in biocompatibility, drug inclusion, cell penetration / reach, surface charge control, sustained release, manufacturing cost, and structural stability. High-function and high-value-added drug carriers that can solve these problems are sought.
[0003] In addition, hollow spherical particles composed of organic polymers from organisms are good platforms for encapsulating or coating various functional substances such as lipids, polymers, proteins, metal nanoparticles, catalysts, magnetic bodies, and carbon materials. They have application prospects in a wide range of fields, such as environmental remediation by absorbing harmful components, removal and harmlessness of heavy metals, biosensors using optical properties, catalytic functions, control of magnetic materials, energy storage, high-functionalization of capacitors, protective coatings, MRI or fluorescence imaging. In addition, by encapsulating capsules composed of biomass from organisms in a matrix such as resin, it is expected to reduce weight and achieve carbon neutrality.
[0004] There are reports on nanoparticles using modified industrial lignin instead of petroleum-derived polymers (Non-Patent Document 1). However, the production process uses organic solvents that are harmful to living organisms and may contain harmful aldehydes or sulfur atoms, which poses a problem in terms of safety.
[0005] Prior art literature
[0006] Non-patent literature
[0007] Non-patent literature 1: M. Lievonen et al. A simple process for lignin nanoparticle preparation, Green Chem. 2016, 18, 1416-1422 (https: / / pubs.rsc.org / en / content / articlelanding / 2016 / gc / c5gc01436k) Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] The technical problem of the present invention is to provide hollow spherical particles that are safer and can be prepared more easily. In addition, preferably, in order to expand the application field, provide hollow spherical particles that are smaller, more stable and / or have various effects and high functions and high added value as described in the background art as a drug carrier.
[0010] Technical means for solving technical problems
[0011] In view of the above technical problems, the inventors of the present invention have conducted in-depth research and found that a hollow spherical particle can solve the above technical problems. It is a hollow spherical particle as a self-assembled body of a lignin-sugar complex, and the above-mentioned lignin-sugar complex is a lignin-sugar complex having at least one bond selected from the group consisting of an α-ether bond between lignin and a polysaccharide, an α-ester bond between lignin and a polysaccharide, and a γ-ester bond between lignin and a polysaccharide. The inventors of the present invention have further studied based on such cognition and completed the present invention. That is, the present invention includes the following aspects.
[0012] That is, the present invention includes the following aspects.
[0013] Item 1. A hollow spherical particle which is a self-assembled body of a lignin-sugar complex, wherein the lignin-sugar complex is a lignin-sugar complex having at least one bond selected from the group consisting of an α-ether bond, an α-ester bond, and a γ-ester bond between lignin and a polysaccharide.
[0014] Item 2. The hollow spherical particle according to any one of the above items, wherein the constituent ratio of the polysaccharide to the lignin in the lignin-sugar complex (the ratio obtained by dividing the number of monomer units of the polysaccharide by the number of monomer units of the lignin) is 0.1 to 10.
[0015] Item 2A. An oil-in-water (O / W) emulsion, double emulsion, vesicle, micelle, capsule, layered structure, or monolayer / multilayer structure, wherein the composition ratio of sugar to lignin in the above-mentioned lignin-sugar complex is 1 to 100% (the percentage of the number of monomer units of sugar to the number of monomer units of lignin).
[0016] Item 2B. A water-in-oil (W / O) emulsion, double emulsion, vesicle, reverse micelle, capsule, layered structure, or single-layer / multilayer structure in which the composition ratio of sugar to lignin in the above-mentioned lignin-sugar complex is 100% or more (the percentage of the number of monomer units of sugar to the number of monomer units of lignin).
[0017] Item 2C. The hollow spherical particles as described in any of the above items are a collection of hollow spherical particles composed of lignin-sugar complexes with an average particle size of 200 nm or more, preferably 250 nm or more, and more preferably 300 nm or more, and the average Zeta potential at pH = 7 and room temperature is positive.
[0018] Item 2D. The hollow spherical particles according to any one of the above items, which are a collection of hollow spherical particles composed of a lignin-sugar complex having an average particle size of less than 200 nm, preferably 150 nm or less, and have a negative average zeta potential at pH = 7 and room temperature.
[0019] Item 3. The hollow spherical particles according to any one of the above items, wherein the molecular weight (Mw) of the lignin-sugar complex is 800 to 10,000, and the polydispersity coefficient (Mw / Mn) is 2.5 or less.
[0020] Item 4. The hollow spherical particles according to any one of the above items, wherein the number average particle size is 1 μm or less.
[0021] Item 5. The hollow spherical particles according to any one of the above items, which contain an active ingredient.
[0022] Item 6. The hollow spherical particles as described in Item 5, wherein the above-mentioned active ingredient is at least one selected from pigments, pesticides, fertilizers, medicines, cosmetic ingredients, fragrances, fluorescent agents, coatings, proteins, antibodies, nucleic acids, vaccines, lipids, hormones, sugars, glycosides, surfactants, adhesives, vitamins, coenzymes, minerals, cells, organelles, low molecular weight compounds, high molecular weight compounds, metal ions, metal nanoparticles, metal complexes, magnetic bodies, liposomes and hydrogels.
[0023] Item 6A. A self-assembly that exhibits electron-donating properties to metal ions in an aqueous solution, wherein the self-assembly is capable of donating electrons corresponding to 1 μmol or more per 1 mg weight of gold (III) ions in an aqueous solution.
[0024] Item 7. The hollow spherical particle according to any one of the above items, which exhibits long-wavelength fluorescence of 450 nm or more.
[0025] Item 8. A drug delivery or introduction agent comprising the hollow spherical particles according to any one of the above items.
[0026] Item 9. A drug delivery or introduction agent according to Item 8, wherein the drug is a nucleic acid.
[0027] Item 10. An ultraviolet absorber comprising the hollow spherical particles according to any one of the above items.
[0028] Item 11. A light resistance-imparting agent comprising the hollow spherical particles according to any one of the above items.
[0029] Item 12. An anti-Stokes fluorescent agent comprising the hollow spherical particles described in any one of the above items.
[0030] Effects of the Invention
[0031] According to the present invention, hollow spherical particles with better biocompatibility, biodegradability, non-toxicity and amphiphilicity and which can be prepared more simply can be provided. In addition, according to the present invention, sustained release, positive and negative surface charges, cell penetration / reachability, stability in water and vacuum, photostability, and selective recognition by ultraviolet absorption and fluorescence absorption can be provided so that the drug can act at an appropriate time in space and time by coating the object or encapsulating / dispersing the drug. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] FIG1-1 is a diagram showing the flow of the M-APA method.
[0033] FIG1-2 is a diagram showing the flow of the A-APA method.
[0034] Figure 2 The diagram shows microwave irradiation conditions and power, temperature, and pressure curves for separation of lignocellulose components. The device is an Initiator+60 microwave synthesis device manufactured by Biotage; stirring speed: 600 rpm; cooling: on; and absorption: high.
[0035] Figure 3 This is a two-dimensional NMR spectrum of low-modification, high-purity, high-ether content lignin. It is the analysis result of lignin separated by the M-APA method (microwave treatment at 50°C, 10 minutes, acetic acid and peracetic acid 1%) using eucalyptus as the starting material.
[0036] Figure 4It is a diagram showing the partial chemical structure of the bonds between lignin units and the covalent bonds between lignin and hemicellulose.
[0037] Figure 5 Two-dimensional NMR spectra ad of lignin-hemicellulose complexes and enlarged images a'-d' of inter-unit bonds and sugar regions. Lignin-hemicellulose complexes obtained from broadleaf trees (a, b) and coniferous trees (c, d) were analyzed using the M-APA method. The circles in the figure represent LC bonds (ether and ester types).
[0038] Figure 6 This is the synchronous fluorescence spectrum of APA lignin from bagasse in the near-infrared wavelength region. It is the result of synchronous scanning measurement to detect a certain Stokes shift, that is, to detect fluorescence wavelengths Em (scanning excitation wavelength) that are 80, 90, 150, 160, and 170 nm longer than the excitation wavelength Ex.
[0039] Figure 7 The 3D fluorescence spectrum of APA lignin of red pine (Pinus densiflora) in the near-infrared wavelength region is shown. Red pine wood powder was treated by the M-APA method (microwave 50°C, 10 min acetic acid + 0.2M hydrogen peroxide conditions), and the resulting APA lignin was measured in 80% acetonitrile solution (concentration 0.1 wt%).
[0040] Figure 8 Shows the UV-visible absorption spectra of the reagent lignin (Tokyo Chemical TCI alkaline lignin, blue line) and lignin (APA lignin, red line).
[0041] Fig. 9 The synchronous back-fluorescence spectra of lignin solid films and lignin-sugar complex solid films are shown. The back-fluorescence spectra (af) and the control (g) are selectively detected by scanning the excitation wavelength to detect the fluorescence that has undergone an anti-Stokes shift shorter than the excitation wavelength. The anti-Stokes shift is -50nm for the excitation wavelength and -40nm for spectrum (b). Comparisons of spectra (b) and (d) and (e) and (f) show that the back-fluorescence intensity is higher when peracetic acid is used as an oxidant than when hydrogen peroxide is used. Comparisons of spectra (b) and (c) show that the back-fluorescence intensity of APA lignin is higher than that of lignin-sugar complex.
[0042] Fig.10 The UV absorption spectra of lignin and lignin-hemicellulose complex are shown. The vertical axis represents absorbance and the horizontal axis represents wavelength (nm). For explanation of the legend, refer to Table 7.
[0043] FIG. 11-1 shows a bright field image of the hollow spherical particles obtained in Reference Test Example 5. FIG.
[0044] FIG. 11-2 shows scanning electron microscope (SEM) photographs of lignin capsules (a, b) and lignin-sugar complex capsules (c) obtained in Example 1. FIG.
[0045] FIG. 12-1 shows a fluorescent image of the hollow spherical particles obtained in Reference Test Example 6. FIG.
[0046] FIG12-2 shows microscopic photographs of the lignin-sugar complex capsules containing the fluorescent pigment DAPI obtained in Example 1. They are fluorescence microscopic photographs (A1, A2), bright field microscopic photographs (B1, B2), and SEM photographs (C1, C2, C3, C4). The fluorescence microscopic photographs show the contained drug. The SEM photographs show that the hollow spherical particles do not break even in a vacuum and can maintain their shape, which indicates the stability of the particle structure.
[0047] Fig.13 It shows the relative value of the average particle diameter of the hollow spherical particles obtained in Example 2. The horizontal axis shows the elapsed time from the time when the hollow spherical particles were prepared.
[0048] Fig.14 It shows the relative value of the average particle size of the hollow spherical particles obtained in Example 2. The horizontal axis shows the temperature during heating and stirring.
[0049] Fig.15 The particle size and zeta potential distribution of eucalyptus lignin capsules (LP, top) and eucalyptus lignin-sugar complex capsules (LHP, bottom) are shown (Example 1).
[0050] Fig.16 The 3D fluorescence spectrum of the lignin-sugar complex capsule is shown. The vertical axis is the excitation wavelength (nm) and the horizontal axis is the fluorescence wavelength (nm).
[0051] Fig.17 The ultraviolet-visible absorption spectrum of the reaction solution is shown (refer to Test Example 3).
[0052] Fig.18 The graph shows the via time and size of sub-micron particles obtained using the electrical resistance nanopulse method (qNANO) (Example 5-2-1).
[0053] Fig.19 The SPM image results are shown, left: 10.00 μm×10.00 μm analysis, right: 2.50 μm×2.50 μm analysis results (Example 5-2-2).
[0054] Fig. 20Represents SPM 3D stereoscopic shape analysis, left: image analysis, right: 3D shape analysis results (Example 5-2-2).
[0055] Fig.21 The results of SPM physical property analysis are shown: left: shape analysis, center: adsorption force analysis, right: hardness analysis (Example 5-2-2).
[0056] Fig. 22 The results of 3D real surface field microscope observation of lignin-sugar complex particles (LCC lignin particles) are shown (Example 5-2-2).
[0057] Fig.23 The figure shows the image data of LCC nanoparticles obtained by interference microscopy (Example 5-2-2).
[0058] Fig.24 The particle size histogram of LCC nanoparticles obtained using an interference microscope is shown (Example 5-2-2).
[0059] Fig.25 The results of particle size evaluation of LCC nanoparticles obtained by DLS are shown (Example 5-2-2).
[0060] Fig.26 The results of measuring the zeta potential of pH 3 lignin fine particles using the resistive nanopulse method (resistive nanopulse method (qNANO)) are shown (Example 5-2-3-1).
[0061] Fig. 27 The results of measuring the zeta potential of lignin fine particles at pH 5 using a resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0062] Fig.28 The results of measuring the zeta potential of lignin fine particles at pH 7 using a resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0063] Fig.29 The results of measuring the zeta potential of lignin fine particles at pH 9 using a resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0064] Fig.30 The results of measuring the zeta potential of p11 lignin fine particles using the resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0065] Fig.31The results of measuring the zeta potential of pH 3 LCC lignin fine particles using the resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0066] Fig.32 The results of measuring the zeta potential of pH 5 LCC lignin fine particles using the resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0067] Fig.33 The results of measuring the zeta potential of pH 7 LCC lignin fine particles using the resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0068] Fig.34 The results of measuring the zeta potential of pH 9 LCC lignin fine particles using a resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0069] Fig.35 The results of measuring the zeta potential of pH 11 LCC lignin fine particles using a resistive nanopulse method (qNANO) are shown (Example 5-2-3-1).
[0070] Fig.36 The results of 3D fluorescence excitation spectrum measurement of LCC lignin fine particles are shown (Example 5-2-4).
[0071] Fig.37 The results of 3D fluorescence excitation spectrum measurement of eosin-composite LCC lignin microparticles (Example 5-2-4) are shown.
[0072] Fig.38 The particle size evaluation results of diethyl sebacate composite fine particles obtained by using DLS are shown (Example 5-2-5).
[0073] Fig.39 The results of fluorescence excitation spectrum measurement of diethyl sebacate composite fine particles are shown (Example 5-2-5).
[0074] Fig.40 A photograph showing hollow spherical particles of a water-in-1-butanol (W / O) lignin-sugar complex (Test Example X). DETAILED DESCRIPTION
[0075] In the present specification, the expressions “comprise” and “include” include concepts such as “comprises”, “includes”, “consists essentially of” and “consists only of”.
[0076] One embodiment of the present invention relates to hollow spherical particles, which are hollow spherical particles (sometimes also referred to as "hollow spherical particles of the present invention" or "self-assembly" in this specification) that are self-assembled bodies of lignin-sugar complexes (sometimes also referred to as "lignin-sugar complexes of the present invention" in this specification), wherein the above-mentioned lignin-sugar complex is a lignin-sugar complex having at least one bond selected from the group consisting of an α-ether bond between lignin and a polysaccharide, an α-ester bond between lignin and a polysaccharide, and a γ-ester bond between lignin and a polysaccharide. The sugar in the lignin-sugar complex of the present specification is derived from a polysaccharide and contains at least one monomer unit that is a sugar. This is described below. 1. Separation method of lignin-sugar complex
[0077] The lignin-sugar complex of the present invention can be obtained by a method for separating lignin from plant biomass (also referred to as "separation method of the present invention" in this specification) comprising the step of (A) contacting a solution containing an organic acid and a peracid with the plant biomass. This is described below.
[0078] The separation method of the present invention includes step (A), and can obtain a high-quality (low-condensation) complex of lignin and polysaccharide having a high content of β-O-4 type ether structure in all bonding forms between monolignols.
[0079] The plant biomass is not particularly limited as long as it contains a lignin-sugar complex, and examples thereof include the plant itself and a machine-processed product of the plant.
[0080] Examples of the plant material include coniferous wood, broadleaved wood, and non-wood materials, and specific examples include cedar, pine, Picea jezoensis, Japanese larch (Larix kaempferi,), black pine (Pinus thunbergii), Sakhalin fir (Abies sachalinensis), Japanese white pine (Pinus parviflora), northeastern yew (Taxus cuspidata), Japanese cedar (Thuja standishii), Japanese spruce (Picea polita), pine spruce (Picea alcoquiana), Podocarpus macrophyllus, Japanese fir (Abies firma), Japanese cypress (Chamaecyparis pisifera), Japanese yellow cedar (Pseudotsugajaponica), Thujopsis dolabrata var. dolabrata, Thujopsis dolabrata var. hondae, Tsuga sieboldii), Japanese hemlock (Tsuga diversifolia), Japanese cypress (Chamaecyparis obtusa), northeastern yew, column crowned torreya (Cephalotaxus harringtonia), spruce (Picea jezoensis var.hondoensis,), yellow cypress (North American golden cypress), Lawson cypress (American cypress), Douglas fir (North American yellow cypress), Sitka spruce (Alaskan spruce), Mondari pine (Pinus radiata), eastern spruce (easternspruce), North American white pine, western larch, western fir, western hemlock, American larch (tamarack) and other coniferous wood; poplar (Populus Tremuloides), American black cherry (American black cherry) cherry), boxwood (Liriodendrontulipifera), walnut, birch, beech, sycamore, silver cherry, ash, teak, Chinese elm, Chinese maple, Indian rosewood, beech, sugar maple, rough bark hickory, long hickory, ash, white oak, white birch, red oak, acacia, eucalyptus and other broad-leaved tree wood; rice, sugarcane, wheat, corn, pineapple, oil palm, hemp, cotton, alfalfa, timothy, bamboo, Japanese arrow bamboo, bamboo, beet and other non-wood materials.
[0081] Examples of machined products of plant bodies include round timber, square timber, boards, solid wood, wooden materials, laminated timber, laminated veneer timber, plywood, artificial boards, particle boards, fiberboards, wood chips, granular wood (wood chips, particles, wood powder, etc.), fibrous wood, pressed products, crushed products, etc.
[0082] From the viewpoint of improving the yield, the plant biomass is preferably wood powder. The volume average particle size of the wood powder is, for example, 500 μm or less, preferably 200 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, and further more preferably 20 μm or less. The lower limit of the average particle size is not particularly limited, and may be, for example, 1 μm, 2 μm or 5 μm. By using wood powder with a smaller particle size, a high yield can be achieved even without the following alkali treatment.
[0083] Wood powder can be obtained by pulverizing plant biomass. The pulverization can be carried out according to or based on a known method, for example, various grinding equipment (such as a ball mill, a stirred mill, etc.) can be used.
[0084] From the viewpoint of improving the yield, the plant biomass is preferably an alkali-treated product of the plant body or its mechanically processed product. According to the present invention, by utilizing the alkali-treated product, the target product can be efficiently obtained even without a pulverization treatment (even in the case of a large specific surface area such as wood chips). The alkali-treated product can be obtained by alkali-treating the plant body or its mechanically processed product. Alkali treatment causes relaxation of the plant cell wall structure (weakening of intermolecular interactions and breaking of hydrogen bonds) and breaking of ester bonds within the molecules, thereby improving the yield. Thus, even if the plant biomass is not physically pulverized or even if the degree of physical pulverization is low, a high yield can be achieved, and the process cost can be reduced. And the yield can be increased to 1.2 to 2 times. In addition, regarding the crystallinity of the cellulose fiber obtained by such an alkali treatment, there will be no significant decrease in crystallinity due to the micro-pulverization treatment, and a clear cellulose Iβ structure is maintained.
[0085] Specifically, the alkali treatment is preferably a step of, for example, (X) bringing the plant body or a machined product thereof into contact with an alkali solution.
[0086] The alkaline solution is not particularly limited as long as it is an alkaline solution of the degree that can achieve the above-mentioned purpose. For example, the alkaline solution can be a solution with a pH of 12 to 15. The pH of the solution is preferably 13 to 14. In addition, the alkaline solution can be, for example, a solution containing 0.3 to 2% by mass (preferably 0.7 to 1.5% by mass) of an alkali metal hydroxide (such as sodium hydroxide, potassium hydroxide, etc.).
[0087] The amount of the alkaline solution used is not particularly limited as long as it is an alkaline solution of a degree that can achieve the above-mentioned purpose. The amount of the alkaline solution can be, for example, 3 to 20 mL, preferably 5 to 12 mL, per 1 g of the plant body or its machined product.
[0088] The manner of contacting the plant body or the machined product thereof with the alkaline solution is not particularly limited, but from the viewpoint of treatment efficiency and the like, it is preferred to immerse the plant body or the machined product thereof in the alkaline solution.
[0089] The temperature of the alkaline solution is not particularly limited as long as it is a temperature that can achieve the above purpose. The temperature of the alkaline solution is, for example, 20 to 150°C, preferably 50 to 120°C, and more preferably 80 to 120°C. When heating, as the method, for example, internal heating method using microwave heating, external heating method using oil bath, etc., etc. can be cited, and internal heating method using microwave heating is preferred.
[0090] The treatment time of step (X) is not particularly limited as long as it is a time sufficient to achieve the above-mentioned purpose. The treatment time is, for example, 5 to 120 minutes, preferably 15 to 60 minutes.
[0091] After step (X), the soluble portion and the insoluble portion may be separated, and the insoluble portion may be subjected to step (A) as an alkali-treated product of the plant body or a mechanically processed product thereof.
[0092] The plant biomass may be a single species or a combination of two or more species.
[0093] The solution containing an organic acid and a peracid (organic acid-peracid solution) contains an organic acid and a peracid and is a solution capable of extracting and solubilizing at least one selected from lignin, hemicellulose, and a lignin-sugar complex, and is not particularly limited within such limits.
[0094] The organic acid is not particularly limited, and examples thereof include acetic acid, formic acid, glyoxylic acid, maleic acid, propionic acid, folic acid, isobutyric acid, valeric acid, isovaleric acid, pyruvic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, ketoglutaric acid, adipic acid, lactic acid, tartaric acid, fumaric acid, oxaloacetic acid, malic acid, isocitric acid, citric acid, benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimellitic acid, trimellitic acid, trimellitic acid, pyromellitic acid, mellitic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, camphorsulfonic acid, p-toluenesulfinic acid, and benzenesulfinic acid. Among these, acetic acid, formic acid, glyoxylic acid, 3-oxopropionic acid, and 2-methyl-3-oxopropionic acid are preferred, acetic acid, formic acid, and glyoxylic acid are more preferred, and acetic acid is particularly preferred.
[0095] The organic acid may be used alone or in combination of two or more.
[0096] There are no particular restrictions on the peracid as long as it is an acid having a hydroperoxide group (-O-OH), and examples thereof include organic peracids such as percarboxylic acids, persulfuric acid, percarbonic acid, perphosphoric acid, and perhalogenous acid. Examples of percarboxylic acids include peracetic acid, performic acid, perbenzoic acid, and meta-chloroperbenzoic acid. In addition, examples of perhalogenous acid include hypochlorous acid, perbromobromic acid, and periodic acid. In addition, in addition to the above, examples of peracids include hydrogen peroxide, lithium peroxide, sodium peroxide, potassium peroxide, sodium percarbonate, urea peroxide, sodium perborate, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, di-tert-butyl peroxide, dimethyl ketone peroxide, acetone peroxide, butanone peroxide, and hexamethylene triperoxide. Among them, organic peroxyacids, hydrogen peroxide, sodium percarbonate, urea peroxide, sodium perborate and the like are preferred, percarboxylic acids (particularly peracetic acid) and hydrogen peroxide and the like are more preferred, and hydrogen peroxide is particularly preferred.
[0097] The peracid may be used alone or in combination of two or more.
[0098] The content of the organic acid in the organic acid-peracid solution is, for example, 5 to 30 mol / L, preferably 8 to 25 mol / L, and more preferably 10 to 20 mol / L. The content of the organic acid in the organic acid-peracid solution is preferably 3 to 10 g, more preferably 4 to 8 g, and even more preferably 5 to 7 g per 1 g of the plant biomass in contact with the organic acid-peracid solution.
[0099] The content of the peracid in the organic acid-peracid solution is, for example, 0.05 to 3 mol / L, preferably 0.08 to 2.5 mol / L, and more preferably 0.1 to 2 mol / L. The content of the peracid in the organic acid-peracid solution is preferably 0.03 to 0.1 g, more preferably 0.04 to 0.08 g, and even more preferably 0.05 to 0.07 g per 1 g of the plant biomass in contact with the organic acid-peracid solution.
[0100] The contact method between the plant biomass and the organic acid-peracid solution is not particularly limited, but from the viewpoint of treatment efficiency and the like, it is preferred to immerse the plant biomass in the organic acid-peracid solution.
[0101] The temperature of the organic acid-peracid solution is not particularly limited as long as it is a temperature at which the lignin-sugar complex can be extracted and solubilized. The temperature of the organic acid-peracid solution is, for example, 60 to 160°C. By setting the temperature to this degree, a high-quality (low-condensation) complex of lignin and polysaccharide with a high content of β-O-4 type ether structure in all bonding modes between monolignols can be obtained. In step (A), there is a tendency that a complex of lignin and polysaccharide is easily obtained when the high-temperature side is treated, while a lignin monomer is easily obtained when the low-temperature side is treated. For example, when the starting material is woody biomass, when step (A) is performed in an organic acid-peracid solution at, for example, 90° C. or less (preferably 40 to 90° C., more preferably 40 to 70° C., and even more preferably 40 to 60° C.), lignin monomers are easily and selectively obtained, and when step (A) is performed in an organic acid-peracid solution at, for example, more than 90° C. and 160° C. or less (preferably 100 to 160° C., and more preferably 120 to 160° C.), a complex of lignin and polysaccharides is easily obtained. For example, when the starting material is herbaceous biomass, when step (A) is performed in an organic acid-peracid solution at, for example, 60° C. or less (preferably 15 to 60° C.), lignin monomers are easily and selectively obtained, and when step (A) is performed in an organic acid-peracid solution at, for example, more than 60° C. and 150° C. or less (preferably 70 to 150° C.), a complex of lignin and polysaccharides is easily obtained. When heating, as the method, for example, internal heating method using microwave heating, external heating method using oil bath etc. can be cited, and internal heating method using microwave heating is preferred. By using rapid internal heating of microwaves, short-time and efficient pretreatment can be achieved.
[0102] The treatment time of step (A) is not particularly limited as long as it is a time sufficient to achieve the above-mentioned purpose. The treatment time is, for example, 1 to 60 minutes, preferably 1 to 30 minutes, and more preferably 5 to 20 minutes.
[0103] In step (A), the microwave treatment is preferably carried out while the biomass is immersed in the above-mentioned solution. Thereby, the yield of lignin is improved. The conditions of the microwave treatment can be appropriately set, for example, a commercially available microwave synthesis device can be used while stirring the solution. The microwave treatment time can be set to, for example, 1 to 30 minutes, preferably about 10 minutes. The separation method of the present invention only requires a short irradiation time during the microwave treatment, and in addition to being easy to construct as a batch system, a continuous system is also easy to construct.
[0104] In step (A), the plant biomass is preferably irradiated with microwaves or ultrasonic waves from the viewpoint of promoting the permeation of the solution into the inner pores of the plant cell wall and improving the yield. The irradiation time is the same as above.
[0105] Step (A) can be carried out by changing the conditions in multiple stages as needed. For example, it can also be carried out while changing the solution temperature. In this case, when comparing a certain stage with the next stage, it is preferred that the solution temperature is higher in the next stage. For example, step (A) may include (A1) a step of contacting a solution containing an organic acid and a peracid at a temperature below 90°C with plant biomass and / or (A2) a step of contacting a solution containing an organic acid and a peracid at a temperature above 90°C and below 160°C with plant biomass. The "plant biomass" in step (A2) includes the insoluble portion obtained in step (A1).
[0106] Through step (A1), the lignin monomer can be selectively extracted and solubilized, and through step (A2), the lignin-sugar complex can be extracted and solubilized. Therefore, by sequentially performing step (A1) and step (A2), the lignin monomer and the lignin-sugar complex can be efficiently obtained.
[0107] After step (A), after adding a separation solvent as needed, the soluble part is separated from the insoluble part. There is no particular limitation on the method for separating the soluble part from the insoluble part, and for example, decantation, centrifugation (spindown), filtration and the like can be used. As a separation solvent, various alcohols such as dioxane, ethanol, acetone, acetonitrile, DMSO, DMF, NMI, ethyl acetate, methanol, butanol, acetic acid, water and their mixed solvents are used to separate lignin and lignin-hemicellulose complexes. From the viewpoint of extraction efficiency, selectivity and environmental load, organic solvents such as acetone, ethanol and acetonitrile and organic solvents mixed with 10 to 20 v / v% of water are preferred.
[0108] Among them, when a non-aqueous extraction solvent (acetic acid-peracetic acid) or separation solvent is used, a high-purity lignin-hemicellulose complex can be obtained. When a water-containing solvent is used, a portion of the hemicellulose component as a polysaccharide can also be obtained at the same time. The hydrolysis reaction can also use a catalyst that promotes the reaction in the presence of an acid or a base.
[0109] The soluble fraction obtained in step (A) contains the lignin-sugar complex. Therefore, the soluble fraction can be obtained as the lignin-sugar complex directly or after other treatment as needed.
[0110] As other treatments, the following treatments can be exemplified. After step (A), water can be removed by rotary evaporation and / or freeze drying as needed to obtain the target product in the form of a dry powder. In addition, when desalination is required, the solvent can be extracted and distilled from the concentrated solution using alcohol or acetone. Thus, the target product can be obtained in the form of a dry powder.
[0111] When the lignin-sugar complex is selectively obtained, for example, the lignin-sugar complex can be obtained from the soluble fraction obtained in step (A2) by using the insoluble fraction obtained in step (A1) as plant biomass.
[0112] According to the present invention, as a new pulping process with low energy consumption and no harmful waste liquid, it is a low-temperature and mild process that utilizes polysaccharides to fully remove lignin. Therefore, it is possible to provide a new plant biomass pretreatment method with less inhibitory substances in the recycled material that cause problems in ethanol fermentation.
[0113] 2. Lignin-sugar complex
[0114] According to the separation method of the present invention, a lignin-sugar complex can be obtained, which has at least the following characteristics: it has at least one bond selected from the group consisting of an α-ether bond between lignin and a polysaccharide, an α-ester bond between lignin and a polysaccharide, and a γ-ester bond between lignin and a polysaccharide.
[0115] <2-1. Lignin>
[0116] The lignin of the present invention refers to lignin separated from biomass (including natural lignin). Natural lignin has various bonding modes. The following are representative bonding modes of natural lignin.
[0117]
[0118] The above-mentioned structure is called β-O-4 bonding.
[0119]
[0120] The above-mentioned structure is called resinol (β-β) bonding.
[0121]
[0122] The above-mentioned structure is called phenylcoumaran (β-5) bonding.
[0123]
[0124] The above method is called 5-5 bonding.
[0125]
[0126] The above-mentioned structure is called dibenzodioxin (DBDO 5-5 / 4-O-β) bonding.
[0127]
[0128] The above method is called 4-O-5 bonding.
[0129]
[0130] The above method is called β-1 bonding.
[0131]
[0132] The above-mentioned manner is called spirodienone bonding.
[0133] In natural lignin, although it varies depending on the plant species, the content of β-O-4 ether structure is the highest among all the bonding forms between monolignols. For example, it is believed that the content is 40-60% in coniferous trees. In addition, in broad-leaved trees, such as eucalyptus, it is believed that the content is about 45%.
[0134] In the lignin of the present invention, the content of the β-O-4 type ether structure in all bonding forms between monolignols is 50% or more, preferably 60% or more, more preferably 65 to 85%, and even more preferably 70 to 80%.
[0135] In the lignin of the present invention, the content (%) of the β-O-4 type ether structure in all bonding forms between monolignols is preferably 1.2x% or more, more preferably 1.4x% or more, and further preferably 1.6x% or more when the content of the lignin contained in the biomass as a raw material is set to x%. In the following text, the upper limit is preferably 2x%.
[0136] In lignin, the content of β-O-4 ether structure in all bonding modes between monolignols is specifically determined as follows. The sample is dissolved in deuterated dimethyl sulfoxide (DMSO-d6) at 1-10wt%, and the NMR spectrum is obtained using a Bruker Avance III 600MHz NMR instrument equipped with a cryogenic probe. The content of β-O-4 ether structure can be estimated based on the signal volume on the HSQC (Heteronuclear single-quantum correlation spectroscopy) spectrum. The quantitative value in the two-dimensional NMR method is corrected according to the literature (H. Okamura, H. Nishimura, T. Nagata, T. Kigawa, T. Watanabe and M. Katahira, Accurate and molecular-size-tolerant NMR quantitation of diverse components in solution, Scientific Reports, 6, 21742.2016) to calculate the accurate content.
[0137] The lignin of the present invention preferably contains 5% or less of biphenyl-type lignin having a condensed structure.
[0138] The number average molecular weight (Mn) of the lignin of the present invention is preferably 0.7 to 9 kDa, more preferably 1 to 5 kDa, and even more preferably 1.5 to 4 kDa.
[0139] The weight average molecular weight (Mw) of the lignin of the present invention is preferably 0.8 to 10 kDa, more preferably 1.5 to 8 kDa, and even more preferably 2 to 6 kDa.
[0140] In the present invention, the number average molecular weight (Mn) and weight average molecular weight (Mw) of lignin are specifically measured as follows. The molecular weight of lignin can be determined by size exclusion chromatography (SEC: Size Exclusion Chromatography) so-called GPC (Gel Permeation Chromatography: Gel Permeation Chromatography). The sample is dissolved in acetic anhydride and a base (pyridine, etc.) solution and reacted for 3 to 6 hours to form an acetyl body. It is dissolved in tetrahydrofuran (THF) at a concentration of 2.0 mg / mL and separated by high performance liquid chromatography. The chromatographic column uses an HZ-M column (Tosoh, 150mm×4.6mm id, 4μm, three columns in series). The analysis is carried out by injecting 10μL of the sample at a column temperature of 40°C, tetrahydrofuran (THF) as the mobile phase, and a flow rate of 0.35mL / min. A mass calibration curve (standard curve) was prepared using standard polystyrene, Tosoh PStQuickC (molecular weight (MW) of 2,110,000, 427,000, 37,900 and 5970), pinoresinol (MW 352) and vanillin (MW 152), and the Mw and Mn of the sample were determined.
[0141] The polydispersity coefficient (Mw / Mn) of the lignin of the present invention is preferably 2.5 or less, more preferably 2 or less.
[0142] <2-2. Lignin-sugar complex>
[0143] The lignin-sugar complex of the present invention refers to a lignin-sugar complex in a state separated from biomass.
[0144] As polysaccharides, for example, xylan and mannan are representative, and glucomannan, galactomannan, glucuronic acid xylan, arabinoglucuronic acid xylan, etc. can be cited. Among them, hemicellulose is mainly composed of glucomannan in conifers, glucuronic acid xylan in broad-leaved trees, and arabinoxylan in herbaceous plants. In the above description, as monomers, xylose, arabinose, glucose, mannose, galactose, and uronic acid are included. In addition, the side chain contains acetyl and methoxy groups. Hemicellulose in herbaceous plants contains products of ferulic acid and diferulic acid bonded to the arabinose side chains of arabinoxylan.
[0145] The lignin-sugar complex of the present invention is a lignin-sugar complex that can be uniformly dispersed in a separation solvent, and is characterized by a high molecular structure formed by copolymerization of lignin and polysaccharides through covalent bonds. The lignin-sugar complex of the present invention is separated by cutting the bonds of a small portion (less than 10% of the number of bonds) of the hemicellulose main chain in the lignin-sugar complex structure in the plant cell wall through a hydrolysis reaction. By carrying out the hydrolysis reaction under mild conditions, over-decomposition, side reactions and low molecular weight can be suppressed.
[0146] The lignin-sugar complex of the present invention is characterized in that it has at least one bond selected from the group consisting of an α-ether bond (LCα-ether bond) between lignin and a polysaccharide, an α-ester bond (LCα-ester bond) between lignin and a polysaccharide, and a γ-ester bond (LCγ-ester bond) between lignin and a polysaccharide.
[0147] In the lignin-sugar complex of the present invention, the α-ether bonds (LCα-ether) between lignin and polysaccharide as copolymerization sites are preferably concentrated to 1.2 times or more of the original bonding unit composition ratio of the raw material biomass.
[0148] In biomass, lignin and polysaccharides can also be bonded by non-covalent bonds. Non-covalent bonds originate from hydrophobic interactions, hydrogen bonds, electrostatic interactions, and entanglement of polymer chains. Therefore, in existing studies, there is no clear evidence that polymers such as lignin and polysaccharides with different properties form a copolymer-like complex through covalent bonds in lignin-sugar complexes. In addition, the preparation of lignin-sugar complexes by existing methods is carried out in multiple stages, with low yield (less than 5%) and low purity.
[0149] Clear evidence of copolymerization sites (covalent bonds) in lignin-hemicellulose copolymers can be confirmed by signal assignment using the HSQC method as a two-dimensional NMR ( Figure 3 , 4). More clear evidence can be confirmed by continuous correlation analysis using HMBC and TOCSY-HSQC methods. For more details, please refer to the literature (Nishimura et al., Direct evidence for αether linkage between lignin and carbohydrates in wood cell walls, SciRep2018) (Nishimura et al., Direct evidence of αester linkages between lignin and glucuronoxylan that reveal the robust heteropolymeric complex in plant cell walls, Research Square https: / / doi.org / 10.21203 / rs.3.rs-1327348 / v1).
[0150] LC α ether
[0151] The CH-related signal at the α-position of lignin (LC ether, δH / δC=4.50±0.15ppm / 80.1±1ppm region) originating from the ether bond between the hydroxyl group at the 6-position of hexose or the 5-position of pentose (e.g., the 6-position of mannose, glucose, galactose and the 5-position of arabinose) and the α-position (benzyl position) of lignin, and the hydroxyl group at the 2-position or 3-position of hexose or pentose (e.g., the 2-position and 3-position of xylose, mannose, glucose, galactose and arabinose) (LC ether, δH / δC=4.95±0.2ppm / 81.5±1.5ppm region).
[0152] LC α ester
[0153] The CH-related signal at the α-position of lignin (LC α ester, δH / δC=5.88±0.15ppm / 74.0±1.5ppm region) originates from the ester bond between the carboxyl group at the 6-position of glucuronic acid (uronic acid) and the α-position (benzyl position) of lignin.
[0154] LC gamma ester
[0155] The CH-related signal at the γ position of lignin originates from the ester bond between the carboxyl group at the 6 position of glucuronic acid (uronic acid) and the γ position of lignin (LC γ ester, δH / δC=4.0±0.15ppm, 4.4±0.15ppm, / 64.8±1.5ppm region).
[0156] The lignin-sugar complex of the present invention has a characteristic that its solubility in 60-80% ethanol (e.g., 60% or 80%) at 25°C is 2w / v% or more. Therefore, by using the lignin-sugar complex of the present invention, it is possible to easily obtain the hollow spherical particles described later without using a solvent that is harmful to the organism, and it is also possible to obtain hollow spherical particles with high stability. The solubility is preferably 4w / v% or more, more preferably 5w / v% or more, further preferably 6w / v% or more, and further more preferably 7w / v% or more. The upper limit of the solubility is not particularly limited, and for example, it can be 40w / v%, 30w / v% or 25w / v%.
[0157] The method for determining the solubility is as follows. After stirring the sample in 25°C ethanol to dissolve it, perform solid-liquid separation to separate it into an ethanol-soluble portion and an ethanol-insoluble portion. Add a 25°C ethanol aqueous solution (1 / 1 = ethanol / water) to the ethanol-insoluble portion, stir and dissolve it, and obtain an ethanol aqueous solution soluble portion. Mix the ethanol aqueous solution soluble portion with the ethanol soluble portion to obtain a sample solution. Among them, the amount of ethanol aqueous solution added is adjusted in such a way that the ethanol concentration of the sample solution reaches a range of 60 to 80%. In the process of obtaining the soluble portion, it is dispersed and solubilized by ultrasonic irradiation as needed. The maximum sample concentration at which the sample solution is transparent when observed with the naked eye is taken as the "solubility in 60-80% ethanol at 25°C".
[0158] The lignin-sugar complex of the present invention preferably has a composition ratio of sugar to lignin of 0.01 to 10.
[0159] The weight average molecular weight (Mw) of the lignin-sugar complex of the present invention is preferably 800 to 15,000, more preferably 2,000 to 10,000, and even more preferably 3,000 to 7,000. The polydispersity coefficient (Mw / Mn) of the lignin-sugar complex of the present invention is preferably 3.5 or less, and more preferably 2.5 or less.
[0160] The measurement methods of the above parameters are based on the measurement methods for lignin of the present invention or the measurement methods of the examples described later.
[0161] 3. Hollow spherical particles
[0162] The hollow spherical particles of the present invention are self-assembled bodies of the lignin-sugar complex of the present invention, and there are no particular restrictions as long as they are hollow spherical. Self-assembly is easy to occur, and the conditions for initiating self-assembly can be set. For example, self-assembly can also be performed in an aqueous solution in which the lignin-sugar complex of the present invention is dispersed to form hollow spherical particles.
[0163] In the above description, specifically, water can be slowly added to a sample dissolved in an organic solvent (alcohol, etc.) to induce self-assembly to form hollow spherical particles. Although the final water ratio is about 95%, once the capsule is formed, it becomes stable in water. In addition, as another method, the sample can be dissolved in water containing alcohol, etc. and allowed to evaporate naturally to form capsules. In this way, submicron-level capsules with high uniformity can be formed.
[0164] Existing lignin (commercially available industrial alkali lignin (Kraft lignin)) does not show dispersibility and solubility in ethanol or water mixed solvents as hydrophilic solvents. The lignin-sugar complex of the present invention shows dispersibility and solubility in hydrophilic solvents and water mixed solvents. Therefore, by using the lignin-sugar complex of the present invention, hollow spherical particles with higher safety for organisms can be obtained.
[0165] The hollow spherical particles of the present invention include a hollow portion, and the number of the hollow portions is not particularly limited. The hollow spherical particles of the present invention may be single-core particles having one hollow portion, or may be multi-core particles having a plurality of hollow portions.
[0166] The self-assembly of the lignin-sugar complex of the present invention shows fluorescence in the long wavelength region. Specifically, fluorescence is shown in the wavelength region of 400nm to 700nm. In addition, in the self-assembly of the lignin-sugar complex of the present invention, fluorescence that has significantly shifted to a shorter wavelength than the excitation wavelength, the so-called anti-Stokes fluorescence, is particularly observed. As an excitation light source, even a light source weaker than a conventional light source, such as a xenon lamp, shows anti-Stokes fluorescence. Therefore, the hollow spherical particles of the present invention can be used as an anti-Stokes fluorescent agent. In this case, for example, the hollow spherical particles of the present invention can be used as anti-Stokes fluorescent coatings, inks and identification agents, (photon) up-conversion type / wavelength conversion molecular raw materials.
[0167] The hollow spherical particles of the present invention are stably dispersed in an aqueous solution and can maintain the above-mentioned fluorescence even in a solid state after drying.
[0168] The number average particle size of the hollow spherical particles of the present invention is, for example, 100 μm or less. In a preferred embodiment of the present invention, the number average particle size of the hollow spherical particles of the present invention is, for example, 10 nm or more. The number average particle size is preferably 30 nm to 30 μm, more preferably 50 nm to 10 μm, further preferably 60 nm to 1 μm, further more preferably 70 nm to 400 nm, and particularly preferably 80 nm to 300 nm.
[0169] The hollow spherical particles of the present invention may have a high internal cavity ratio. The internal cavity ratio of the hollow spherical particles of the present invention is, for example, 60% or more, preferably 70% or more, more preferably 75% or more, and further preferably 80% or more. The internal cavity ratio is measured by the method described in Reference Test Example 6.
[0170] The hollow spherical particles of the present invention can contain active ingredients in the hollow part, for example, they can be used as a transport carrier for substances, etc. In addition, dissolution resistance, compatibility, light resistance, etc. can be imparted to the active ingredients. As active ingredients, a wide range of options can be selected, for example, pesticides, fertilizers, medicines, cosmetic ingredients, fragrances, fluorescent agents, coatings (such as vanillin, limonene, menthol, etc.), proteins, antibodies, nucleic acids (such as oligonucleotides such as DNA and RNA), vaccines, peptides, lipids, hormones, sugars, glycosides, surfactants, ultraviolet absorbers, light scatterers, adhesives, vitamins, coenzymes, minerals, cells, organelles, low molecular weight compounds (such as information transmission substances such as pheromones, nitrogen-containing compounds such as alkaloids, monoterpenes, sesquiterpenes, isoprenoid compounds such as terpenes, phenylpropanoid compounds, etc.), polymer compounds, metal complexes, liposomes, hydrogels, etc.
[0171] Specifically, the hollow spherical particles of the present invention can be used as drug carriers (DDS applications). More specifically, they can be used as organic capsules as drug carriers. Since they are natural products, they are expected to have biocompatibility and are therefore effective as drug carriers. Moreover, hollow spherical particles having an average particle size of less than 200 nm, preferably less than 100 nm, will not leak into normal tissues, and are expected to achieve the EPR effect (Enhanced Permeation and Retention Effect) of reaching and accumulating in tumor tissues.
[0172] The hollow spherical particles of the present invention can also be used as ultraviolet absorbing capsules for the purpose of imparting light resistance to protect the contained compound from ultraviolet damage. Since the absorption region includes the wavelength region of UV-A and UV-B, it is also effective as an ultraviolet absorbing material used in skin care products such as sunscreen. It is speculated that this ultraviolet absorption effect is caused by intermolecular interactions such as π-π stacking of aromatic lignin.
[0173] The hollow spherical particles of the present invention also include cationic particles, which have a high affinity for negatively charged cell membranes and are easily taken into cells. Therefore, they are useful as drug carriers and can be used as drug delivery or introduction agents. In addition, the hollow spherical particles of the present invention can form ion complexes with negatively charged nucleic acids on the surface of the hollow spherical particles, and are therefore useful as nucleic acid carriers and can be used as nucleic acid delivery or introduction agents. The hollow spherical particles of the present invention can have a positive charge, for example, a Zeta potential of 5 to 100 mV, preferably 10 to 80 mV, more preferably 20 to 60 mV, and further preferably 40 to 60 mV.
[0174] In one embodiment of the present invention, the hollow spherical particles of the present invention are a collection of hollow spherical particles composed of lignin sugar complexes with an average particle size of 200 nm or more, preferably 250 nm or more, and more preferably 300 nm or more, and the average Zeta potential at pH = 7 and room temperature is positive. In addition, in one embodiment of the present invention, the hollow spherical particles of the present invention are a collection of hollow spherical particles composed of lignin sugar complexes with an average particle size of 200 nm or less, preferably 150 nm or less, and the average Zeta potential at pH = 7 and room temperature is negative. Zeta potential can be measured using a resistive nanopulse method. Room temperature refers to a temperature of about 20°C, for example 20°C.
[0175] The hollow spherical particles of the present invention are positively charged at neutral to acidic pH, can be stably dispersed in water for a long time, and as shown in Example 3, by making the pH of the external environment alkaline, the conversion from negative charge to positive charge can be achieved with almost no change in particle size, and have the function of pH-responsive nanocarriers.
[0176] The hollow spherical particles of the present invention may be particles in which liquid, gas or solid (one of which is metal) is enclosed. In this case, the hollow spherical particles of the present invention can be used as, for example, a heat insulating material, a compatibilizer, a catalyst or a sensitizer.
[0177] The presence of the above-mentioned active ingredients, solids, etc. is not particularly limited as long as they are in contact with and retained in the hollow spherical particles. Examples thereof include a presence in the hollow portion of the hollow spherical particles, a presence retained or attached to the constituent components (lignin) of the hollow spherical particles, a presence retained or attached to the outer surface of the hollow spherical particles, and the like.
[0178] The hollow spherical particles of the present invention show long-wavelength fluorescence. Originated from the formation of associations between molecules of the conjugated system and inside the polymer due to the self-assembly of lignin, i.e., the formation of so-called J complexes, long-wavelength fluorescence caused by the formation of exciplexes, preferably fluorescence above 450nm, more preferably fluorescence above 480nm, further preferably fluorescence of 500 to 600nm (specifically, for example, Ex 515nm / Em 535nm) and large Stokes shift fluorescence of more than 100nm (for example, Ex 410nm / Em 670nm) can be observed. Fluorescence in the long-wavelength region can be effectively used for the identification of hollow spherical particles. In particular, fluorescence above 600nm in the near-infrared region is called a biological window, which is suitable for selective optical detection purposes that do not overlap with coexisting components, dynamic tracking of drugs in vivo, and imaging purposes.
[0179] The hollow spherical particles of the present invention, which are self-assemblies of lignin-sugar complexes, can also suppress association / aggregation over time and can maintain their particle size more stably. The stability (dispersion maintenance, structural stability, temperature stability) of the hollow spherical particles can be evaluated by the rate of change of the average particle size after 6 weeks of production when measured under the conditions of Example 2. Regarding the stability of the hollow spherical particles (rate of change of the average particle size), the rate of change after 6 weeks is within ±13% relative to the average particle size of 100% just after production. The temperature stability of the hollow spherical particles is particularly excellent, and the rate of change of the average particle size is within ±20% (in the range of 10°C-60°C), preferably within ±5% (in the range of 10°C-70°C). Therefore, the stability (6 weeks) of the hollow spherical particles of the present invention is expressed as a rate of change within 15%, and preferably the thermal stability is within 5%.
[0180] In addition, the structural stability can also be evaluated by scanning electron microscope observation. That is, as shown in Example 1 (Figure 11-2), even the dry capsule can maintain the hollow spherical structure in a vacuum. As shown in Example 1 (Figure 12-2), the structure is also stable after the drug is encapsulated. Such shape stability can be used for efficient formulation, accumulation, transportation, and storage of drug carriers.
[0181] The particle size, surface charge, dispersibility, and encapsulation performance of the lignin-sugar complex capsules of the present invention, which are hollow spherical particles, can be widely adapted to the plant species and parts of the raw material biomass.
[0182] This difference originates from the structural unit ratio of lignin in the lignin-sugar complex (the composition ratio of the aromatic core structure with phenylpropane unit as the basic skeleton, guaiacyl lignin, syringyl lignin, p-hydroxyphenyl lignin and flavonoid lignin) and the type of polysaccharide.
[0183] In addition, the particle size, surface charge, dispersibility and encapsulation performance of the lignin-sugar complex capsules of the present invention as hollow spherical particles can be widely coped with according to the lignin-sugar composition ratio (the ratio obtained by dividing the number of monomer units of polysaccharide by the number of monomer units of lignin) in the constituted lignin-sugar complex and the separation of polysaccharide types.
[0184] Lignin-sugar complexes with different lignin-sugar composition ratios can be easily separated by using the difference in solubility in alcohol / water or dioxane / water, etc. In addition, they can also be separated by hydrophobic interaction chromatography (the method described in the literature (Nishimura et al., Direct evidence for αether linkage between lignin and carbohydrates in wood cell walls, Sci Rep 2018), TOYOPEARL HW50 column).
[0185] The polysaccharide component in the lignin-sugar complex is hemicellulose. In the case of broadleaf raw materials, it contains a large amount of acidic polysaccharides containing uronic acid (glucuronic acid xylan), and in the case of coniferous trees, it contains a large amount of neutral polysaccharides (glucomannan). The separation of the polysaccharide components of the lignin-sugar complex can be carried out using the ion exchange chromatography described in the literature (Nishimura et al., Direct evidence for αether linkage between lignin and carbohydrates in wood cell walls, Sci Rep 2018).
[0186] The hollow spherical particles of the present invention can control the sustained release by allowing the enzyme as a biocatalyst to act. As shown in Example 4, by allowing the polysaccharide degrading enzyme to act, the shape of the hollow spherical particles carrying the drug can be changed or disintegrated to release the drug. The enzyme has substrate specificity, pH and temperature conditional selective activity. By using the enzyme (hydrolase, oxidase) corresponding to the target, the control of the sustained release conditions (pH, temperature, release rate) can be achieved.
[0187] The use of the lignin-sugar complex of the present invention to encapsulate and coat effective ingredients such as metal nanoparticles can improve functionality in many aspects. It can improve the dispersibility and sustainability of particles in water, and can also bring about good dispersibility of particles in a dry state, as well as compatibility with matrices containing resins, etc. This enables metal nanoparticles to be used in a variety of environments, and by providing hydrophobicity to organic solvents, solubility and dispersibility are improved. This is a characteristic required in many industrial applications. These coatings can also maintain the chemical stability of metal nanoparticles or metal ions, and can impart the ability to control their reactivity. As a result, these particles can function as catalysts or sensors. By improving biocompatibility, environmental affinity, photoresponsiveness, and molecular recognition capabilities, it can be used for biomedical applications, environmental remediation, optical devices, biosensors, and other uses. By imparting sustained release, it is possible to achieve controllable substance release or functional expression over time, which is particularly effective as a drug delivery application. By improving weather resistance and light resistance, the durability of encapsulated components and metal ions to the external environment is improved. In addition, the control of particle size helps to improve safety, optimize performance, and enhance environmental adaptability and biocompatibility.
[0188] The present invention can specifically bring about the following improvements, modifications, application expansion, and performance enhancements of metal nanoparticles.
[0189] Gold (Au) nanoparticles are used in biomedical fields such as sensors using surface plasmon resonance (SPR), imaging, carriers in drug delivery systems (DDS), target selectivity, and photothermal therapy using photothermal conversion properties achieved by light irradiation. It is expected that they will be widely used as catalysts for chemical reactions in organic synthesis reactions and electrode materials for fuel cells, air and water purification, etc. Silver (Ag) nanoparticles have uses as antibacterial agents using their antibacterial properties and as conductive inks. Platinum (Pt) nanoparticles are widely used, especially as catalysts for fuel cells, and are also effectively used as catalysts in the chemical industry. Palladium (Pd) nanoparticles are particularly useful as catalysts, and are used in carbon-carbon bond formation reactions and hydrogenation reactions, etc., and are expected to be used as hydrogen storage materials. Iron (Fe) nanoparticles can be used as contrast agents for MRI and components of magnetic fluids, and can also be expected to decompose harmful substances in groundwater. Copper (Cu) nanoparticles can be expected to be used as conductive inks and as catalysts for decomposing atmospheric pollutants, etc.
[0190] Nickel (Ni) nanoparticles can be used in data storage or magnetic ink, magnetic fluid, etc. due to their strong magnetism. They can also be used as catalysts in hydrogenation reactions or energy conversion. Titanium (Ti) nanoparticles can be used as photocatalysts in the form of titanium dioxide (TiO2). They have self-cleaning materials and water / air purification functions. They can also be used in bioimaging and drug delivery. Zinc (Zn) nanoparticles can be used in solar power generation and LEDs, UV protection agents, cosmetics, etc. Aluminum (Al) nanoparticles can be used as energy generation (rocket propellants, etc.) and thermal conductive materials.
[0191] Example
[0192] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.
[0193] Reference Test Example 1. Lignin, lignin-sugar complex, hemicellulose, cellulose-hemicellulose complex and Separation of cellulose
[0194] By using the M-APA method, the A-APA method or the conditional study method thereof, lignin, lignin-sugar complex, hemicellulose, cellulose-hemicellulose complex and cellulose are separated from biomass, and the yield is measured, the physical properties of the separated products are measured, etc. The separation method of the present invention is a method for efficiently separating soluble lignin, lignin-sugar complex, hemicellulose, cellulose-hemicellulose complex and cellulose from natural polymers in biomass, and includes a step (A) of contacting a solution containing an organic acid and a peracid with plant biomass. The specific method is as follows.
[0195] <Reference Test Example 1-1. Preparation of finely pulverized wood powder>
[0196] A fine powder (micro-crushed wood powder) having a volume average particle size of 10 μm (1-100 μm) is prepared from wood powder of broad-leaved trees (eucalyptus or beech), coniferous trees (pine, Japanese cedar or Japanese cypress) or herbaceous plants (bagasse (sugarcane) or bamboo) using a ball mill or a bead mill.
[0197] An example of the preparation method using a ball mill is shown. A planetary ball mill (P-6, Fritsch) was used. 2 g of wood powder and 100 g of zirconia beads were placed in an 80 cc agate container and sealed in a double stacked grinding bowl (overpot). After the stacked grinding bowl was evacuated for 20 minutes, nitrogen was injected as an inactive gas. The grinding time was 1 minute and the pause time was 1 minute and 20 seconds as a cycle, and 180 cycles (3 hours in total) were performed at 550 rpm. According to the above conditions, fine wood powder can be obtained while suppressing the oxidation during crushing and the denaturation caused by heating.
[0198] <Reference Test Example 1-2. Preparation of wood flour>
[0199] 1 g of wood powder or wood chips (10 mm × 10 mm × 1 mm) of broad-leaved trees (eucalyptus or beech), coniferous trees (Japanese pine, Japanese cedar or Japanese cypress) or herbaceous plants (bagasse (sugarcane) or bamboo) were placed in the left and right grinding bowls of a stirred mill (MM301, manufactured by Retsch), and the powder or wood chips were pulverized under the conditions of pulverization time of 5 minutes and frequency of 1 / 15 second to obtain a powder (wood powder) with a volume average particle size of 0.1 mm.
[0200] <Reference Test Example 1-3. M-APA method (Milling-Acid-PerAcid method)>
[0201] As the starting material, the finely pulverized wood powder (average particle size 10 μm) obtained in Reference Test Example 1-1 was used. 2 g of finely pulverized wood powder and 10 mL of a solution containing acetic acid-peracetic acid (composition: 99% acetic acid, 17.4 M; slightly less than 1% peracetic acid, 0.14 M; hydrogen peroxide 0.01 M, trace amount of water) were added to an Initiator vial, and microwave irradiation was performed for 10 minutes using an Initiator+60 microwave synthesis device manufactured by Biotage at 50°C, an initial power of 400 W, and a stirring speed of 600 rpm. After microwave treatment, 10 mL of a separation solvent (acetone) was added to the soluble portion, and the portion was separated by centrifugation (RCF 8000xg, 5 minutes). The insoluble portion was extracted and washed 3 times with 10 mL of a separation solvent (acetone), and then combined with the soluble portion. The soluble lignin was made into acid peracid lignin (APA lignin).
[0202] For the insoluble fraction, as the second stage, the microwave heating conditions were changed to 140°C and the same extraction operation was performed. The soluble fraction is a lignin-hemicellulose complex. The insoluble fraction containing cellulose as the main component was obtained.
[0203] <Reference Test Example 1-4. A-APA method (Alkali-Acid-PerAcid method)>
[0204] As the starting material, the wood powder (average particle size 0.1 mm) obtained in Reference Test Example 1-2 was used. A 0.25 M sodium hydroxide solution was prepared (1N was diluted 4 times). 2.4 mL of 0.25 M sodium hydroxide solution was added to 0.3 g of wood powder and subjected to microwave extraction (100° C., 30 min). The base requirement was 1 mmol of NaOH per 1 g of wood powder.
[0205] After microwave treatment, the soluble part and the insoluble part can be easily separated by decantation, centrifugation and filtration. Three additional extractions were performed with acetone (separation solvent) and combined with the soluble part. For the insoluble part, the acid peracid lignin (APA lignin) and lignin-hemicellulose complex as soluble lignin were obtained by the same extraction method as the M-APA method of Reference Test Example 1-3. An insoluble part with cellulose as the main component was obtained.
[0206] <Reference Test Example 1-5. Study of Conditions>
[0207] Other organic acids (formic acid, glyoxylic acid) were used instead of acetic acid for the study. In addition, other peracids (hydrogen peroxide) were used instead of peracetic acid for the study. The composition when other peracids (hydrogen peroxide) were used was acetic acid: 12M, hydrogen peroxide concentration: the concentrations shown in the table below.
[0208] The contact temperature between the plant biomass or the insoluble fraction and the organic acid + peracid was changed to room temperature to 180° C. In addition, as the heating method at this time, an external heating method using an oil bath was used instead of an internal heating method using microwave heating.
[0209] <Reference Test Example 1-6. Analysis and Measurement Methods>
[0210] Lignin, lignin-sugar complex and cellulose were analyzed and measured according to the following methods.
[0211] <Reference Test Example 1-6-1. Molecular weight (Mn, Mw and polydispersity coefficient) measurement method>
[0212] The molecular weight is determined by size exclusion chromatography (SEC) called GPC (Gel Permeation Chromatography). The sample is dissolved in acetic anhydride and a base (pyridine, etc.) solution and reacted for 3 to 6 hours to form an acetyl body. It is dissolved in tetrahydrofuran (THF) at a concentration of 2.0 mg / mL and separated by high performance liquid chromatography (manufactured by Shimadzu Corporation, high pressure gradient SEC analysis system). The chromatographic column used is an HZ-M column (Tosoh, 150 mm×4.6 mm id, 4 μm, three columns in series). The analysis is carried out by injecting 10 μL of the sample at a column temperature of 40°C, tetrahydrofuran (THF) as the mobile phase, and a flow rate of 0.35 mL / min. A mass calibration curve (standard curve) was prepared using standard polystyrene, Tosoh PSt Quick C (molecular weight (MW) of 2,110,000, 427,000, 37,900 and 5970), pinoresinol (MW 352) and vanillin (MW 152) to determine the weight average molecular weight Mw and number average molecular weight Mn of the sample. The polydispersity coefficient was determined as Mw / Mn.
[0213] <Reference Test Example 1-6-2. Calculation method of constituent ratio of bonding units in a molecule>
[0214] The sample was dissolved in deuterated dimethyl sulfoxide (DMSO-d6) in a manner of 1-10wt%, and the NMR spectrum was obtained using a Bruker Avance III 600MHz NMR instrument equipped with a cryogenic probe. The composition ratio of the inter-unit bonding unit of lignin was calculated based on the signal volume on the HSQC (Heteronuclear single-quantum correlation spectroscopy) spectrum. The composition ratio was calculated as the ratio per 100 lignin aromatic rings. The content of the ether-type bonding unit was estimated based on the sum of the integrated values of the CH-related signals at the β position (the region of δH / δC=4.0±0.2ppm / 85.6±1.2ppm, the region of δH / δC=4.3±0.2ppm / 83.0±0.7ppm). The quantification by the two-dimensional NMR method was corrected by the TAF method described in the literature (Okamura, H. Nishimura, T. Nagata, T. Kigawa, T. Watanabe and M. Katahira, Accurate and molecular-size-tolerant NMR quantitation of diverse components insolution, Scientific Reports, 6, 21742.2016) to calculate the accurate content.
[0215] <Reference Test Example 1-6-3. Calculation method of the composition ratio of lignin to polysaccharide>
[0216] The total integrated value of the CH related signal at the abnormal position (1st position) of the polysaccharide was calculated by the NMR method described in the previous item, and after correction by the TAF method, it was calculated as a ratio per 100 lignin aromatic rings.
[0217] <Reference Test Example 1-6-4. Calculation method of the composition ratio of lignin-sugar copolymerization sites>
[0218] As described above, the sum of the integrated values of the CH-related signals (LC ether, δH / δC=4.50±0.15ppm / 80.1±1ppm region) and (LC ester, δH / δC=5.88±0.15ppm / 74.0±1.5ppm region) from the bonding units of LCα ether and LCα ester is calculated by the two-dimensional HSQC NMR method, and after correction by the TAF method, it is calculated as the ratio per 100 lignin aromatic rings. In the case of the A-APA method, some ester bonds are hydrolyzed by alkali treatment, but LCα ester-type lignin-hemicellulose complexes can also be obtained.
[0219] <Reference Test Example 1-6-5. Calculation method of yield from raw material biomass>
[0220] After confirming the obtained components using a pH meter or pH test paper, peracid test paper (potassium iodide starch test paper), neutralization and peracid quenching are carried out as needed. Neutralization is carried out by adding 1N HCl or 1N NaOH in small amounts. Peracid quenching is carried out by dropping 1M sodium sulfite aqueous solution. The organic solvent is removed by an evaporator. Then, a dry powder is obtained by freeze-drying. In the case of salt generated by neutralization, the concentrated solution after distillation of the organic solvent is extracted and desalted again with a separation solvent (acetone). Then, after evaporating the solvent again by an evaporator, a dry powder is obtained by freeze-drying. Weigh the obtained components and calculate the yield per unit of raw biomass.
[0221] <Results>
[0222] The molecular structure, molecular weight and yield of the polymer obtained under the following conditions were preferred. The results are shown in Tables 1 to 7.
[0223] Table 1 shows the peracid conditions and the yields of each component of high molecular weight lignocellulose in the two-stage microwave extraction reaction of the M-APA method (weight %, raw material biomass ratio, raw material is eucalyptus).
[0224] [Table 1]
[0225]
[0226] Table 2 shows the yields (weight %, raw material biomass ratio) of each component of high molecular weight lignocellulose from various biomasses in the two-step microwave extraction reaction of the A-APA method.
[0227] [Table 2]
[0228]
[0229] Table 3 shows the peracid conditions in the two-step microwave extraction reaction of the M-APA method and the molecular weights (acetyl bodies GPC analysis values) of the components of the high molecular weight lignocellulose.
[0230] [Table 3]
[0231]
[0232] Table 4 shows the yields (weight %, raw material biomass ratio) of each component of high molecular weight lignocellulose from various biomasses in the two-step microwave extraction reaction of the M-APA method.
[0233] [Table 4]
[0234]
[0235] Solvent: Acetic acid (containing 1% peracetic acid 0.14 mol / L)
[0236] Microwave extraction conditions: The APA lignin soluble part was obtained at 50°C and 10 min (first stage), and the lignin hemicellulose complex was obtained at 140°C and 10 min (second stage). Table 5 shows the yields (weight %, raw biomass ratio) of each component of high-molecular-weight lignocellulose in various biomass in the first-stage microwave extraction reaction of the A-APA method.
[0237] [Table 5]
[0238]
[0239] Table 6 shows the molecular weights (acetyl bodies GPC analysis values) of each component of high molecular weight lignocellulose obtained by the A-APA method for various biomasses.
[0240] [Table 6]
[0241]
[0242] The results of the condition study show that when the starting material is woody biomass, the contact temperature with organic acid + peracid of 40 to 90°C is suitable for obtaining soluble lignin, and the contact temperature with organic acid + peracid of 100 to 160°C is suitable for obtaining lignin-hemicellulose complexes. In addition, the results of the condition study show that when the starting material is herbaceous biomass, the contact temperature with organic acid + peracid of room temperature to 60°C is suitable for obtaining soluble lignin, and the contact temperature with organic acid + peracid of 70 to 150°C is suitable for obtaining lignin-hemicellulose complexes.
[0243] The results of the condition study show that the heating time using microwave irradiation is 5 to 30 minutes, preferably 10 minutes. The net irradiation time is short, and the microwave curve and temperature and pressure data refer to Figure 2 .
[0244] The results of the condition study showed that microwave heating has higher yield and selectivity under low temperature, short time and low energy input conditions compared with external heating. In other words, the microwave effects of local heating, internal heating, electron transfer and drug penetration enhancement were confirmed.
[0245] The results of the condition study showed that, as organic acids, acetic acid, formic acid, and glyoxylic acid can all be used to separate lignin, but acetic acid is most preferred from the viewpoints of yield, purity, and industrial applicability.
[0246] Figure 3 The NMR results of Reference Test Example 1-6-2 and Reference Test Example 1-6-3 are shown. Figure 3This is the analysis result of lignin separated by the M-APA method (microwave treatment at 50°C, 10 minutes, acetic acid and peracetic acid 1%) using eucalyptus as the starting material. The ratio of bonds between lignocellulose units was quantified by the TAF-NMR method, and the result showed that the signal peak from lignin was 99%, and the signal peak from polysaccharide (hemicellulose) was 1%. The details of the bonds between lignin units are: ether type β-O-4 is 81%, β-5 is 5%, β-β is 11%, dibenzodioxazine is 1%, and others are 1%. For the partial chemical structure of the bonds between lignin units and the covalent bonds between lignin and hemicellulose, please refer to Figure 4 .
[0247] Figure 5 The NMR results of Reference Test Example 1-6-4 are shown. Figure 5 The results of the analysis of the lignin-hemicellulose complex separated by the M-APA method (microwave 50°C, 10 minutes treatment, acetic acid and peracetic acid 1%) using each plant as the starting material are shown. The LC bonds (ether type and ester type) shown in the circle in the figure are the main branch structures that exist in the same or higher ratio of the main inter-unit bonds β-5 and β-β bonds of lignin. The separated lignin-hemicellulose complex is characterized by having LC α-ester type bonds in particular.
[0248] Reference Test Example 2. Solubility Determination
[0249] The solubility of lignin and lignin-hemicellulose complex obtained by the method of Reference Test Example 1 or a method based thereon in 60-80% ethanol at 25°C was measured. Detailed information of the measured samples is shown in Table 7. The abbreviations in Table 7 are as follows. In addition, the same abbreviations may be used in the following description.
[0250] PA: PerAcetic acid
[0251] HP:Hydrogen Peroxide
[0252] 50: MW50 ACTN, microwave 50℃ treatment of high-quality polymer lignin
[0253] 140: MW50-Mw140 ACTN, residue after microwave treatment at 50°C, second stage treatment at 140°C, lignin hemicellulose complex
[0254] A50: Acetic acid, peroxyacetic acid system, HP PA1% AA Mw50 ACN microwave 50℃ treated high quality polymer lignin
[0255] H50: Acetic acid hydrogen peroxide system, HP 1M hydrogen peroxide Mw50 ACN microwave 50℃ treated high quality polymer lignin.
[0256] [Table 7]
[0257] EA50 Eucalyptus wood chips Acetic acid, peracetic acid, PA1%AA Mw50 ACTN EA140 Eucalyptus wood chips Acetic acid, peracetic acid, PA1%AA Mw 50-Mw140 ACTN EH50 Eucalyptus wood chips Acetic acid hydrogen peroxide system, HP 1M hydrogen peroxide Mw50 ACN BH50 Japanese beech sapwood Acetic acid hydrogen peroxide system, HP 1M hydrogen peroxide Mw50 ACN PH50 Japanese red pine sapwood Acetic acid hydrogen peroxide system, HP 1M hydrogen peroxide Mw50 ACN CH50 Japanese cedar sapwood Acetic acid hydrogen peroxide system, HP 1M hydrogen peroxide Mw50 ACN CH140 Japanese cedar sapwood Acetic acid Peracetic acid system, HP 1M Hydrogen peroxide Mw 50- Mw140 ACTN TA50 Japanese bamboo powder Acetic acid, peracetic acid, PA1%AA Mw50 ACTN TA140 Japanese bamboo powder Acetic acid, peracetic acid, PA1%AA Mw 50- Mw140 ACTN HP50 Japanese bamboo powder Acetic acid hydrogen peroxide system, HP 1M hydrogen peroxide Mw50 ACN
[0258] The method for determining the solubility is as follows. After the sample is stirred and dissolved in ethanol at 25°C, it is separated into an ethanol-soluble portion and an ethanol-insoluble portion by solid-liquid separation. A 25°C ethanol aqueous solution (1 / 1 = ethanol / water) is added to the ethanol-insoluble portion and stirred to dissolve, thereby obtaining an ethanol aqueous solution soluble portion. The ethanol aqueous solution soluble portion is mixed with the ethanol soluble portion to obtain a sample solution. Among them, the amount of ethanol aqueous solution added is adjusted so that the ethanol concentration of the sample solution is in the range of 60 to 80%. In the process of obtaining the soluble portion, it is dispersed and solubilized by ultrasonic irradiation as needed. The maximum sample concentration at which the sample solution is transparent when observed with the naked eye is set as "solubility in 60 to 80% ethanol at 25°C".
[0259] The results are shown in Table 8. The lignin and lignin-hemicellulose composite obtained by the method of the present invention showed a solubility of 8 to 20% in ethanol / water solutions (60 / 40 and 80 / 20 v / v%).
[0260] [Table 8]
[0261] Solubility EA50 8w / v% in 80% ethanol aqueous solution EA140 8w / v% in 80% ethanol aqueous solution EH50 15w / v% in 60% ethanol aqueous solution BH50 20w / v% in 60% ethanol aqueous solution PH50 20w / v% in 60% ethanol aqueous solution CH50 8w / v% in 70% ethanol aqueous solution CH140 20w / v% in 60% ethanol aqueous solution TA50 8w / v% in 80% ethanol aqueous solution TA140 8w / v% in 80% ethanol aqueous solution HP50 15w / v% in 60% ethanol aqueous solution
[0262] Reference Test Example 4. Preparation and Analysis of Self-Assembly
[0263] Self-assembly was prepared using lignin separated by the M-APA method (microwave 50°C, treatment for 10 minutes, acetic acid-peracetic acid 1% or acetic acid-0.2M hydrogen peroxide conditions) using eucalyptus or bamboo as a starting material, or lignin-sugar complex separated by the M-APA method (microwave 140°C, treatment for 10 minutes, acetic acid-peracetic acid 1% or acetic acid-0.2M hydrogen peroxide conditions) using eucalyptus as a starting material as a sample. The specific method was as follows.
[0264] Prepare a DMSO solution with a sample concentration of 1-2wt%, and dilute it to 0.01-0.02wt% using a mixed solvent (1:1 or 2:1) of a separation solvent (acetonitrile or ethanol) and water (or buffer) to obtain a sample solution. Apply 0.1-0.2mL of the sample solution to a slide glass or a cover glass, and volatilize the solvent under atmospheric pressure to obtain a thin film self-assembly. Under the above conditions, a high concentration of self-assembly can be obtained by adding an equal amount of water (or buffer) to a DMSO solution with a sample concentration of 1wt% and applying it.
[0265] Next, the optical properties of the obtained self-assembly (lignin solid film or lignin-sugar complex solid film) and a comparative object (lignin obtained by the APA method (APA lignin)) were analyzed as follows.
[0266] The following apparatus was used for the measurement.
[0267] Ultraviolet visible absorption spectrum: UV-2700 (manufactured by Shimadzu Corporation)
[0268] Fluorescence spectrum: Spectrofluorophotometer RF-6000 (manufactured by Shimadzu Corporation)
[0269] Fluorescence microscope measurement: integrated fluorescence microscope BZ-X810 (manufactured by KEYENCE Corporation)
[0270] The analysis was performed using the analysis software provided with each device.
[0271] UV-visible absorption spectrum: black quartz cuvette for spectrophotometry (optical path length: 10 mm)
[0272] Fluorescence measurement: A synthetic quartz cuvette (optical path length: 10 mm) with all surfaces transparent and a Starna triangular prism quartz cuvette SF3 were used. Solid samples were measured using a solid measurement unit, and the sample applied on a cover glass was clamped between quartz plates to fix it.
[0273] The 3D fluorescence spectrum was measured under the following conditions: excitation wavelength 310-800nm, data interval 5nm, fluorescence wavelength 350-900nm, data interval 1nm, scanning speed 12000nm / min, scattered light, and UV cutoff filter U310 was installed on the excitation side to reduce the influence of multiple light. The bandwidth was 5nm on the excitation side and 15nm on the fluorescence side, and the sensitivity was set to Low.
[0274] Synchronous scanning spectroscopy is a scanning mode in which the excitation spectrometer and the fluorescence spectrometer of the spectrofluorometer are scanned simultaneously with a certain wavelength interval. The wavelength interval of the excitation light and the fluorescence is changed in the range of -90nm to 260nm for measurement. When the wavelength interval is negative, the fluorescence with a wavelength shorter than that of the excitation light is detected. At this time, the fluorescence caused by the anti-Stokes shift can be selectively detected. The scan is set to cover the fluorescence wavelength range of 350-800nm, the data interval is 0.1nm, the scanning speed is 600nm / min, the bandwidth is 15nm on the excitation side, 20nm on the fluorescence side, and the sensitivity is set to Low.
[0275] The UV-visible absorption spectrum was measured using a double monochromator UV-2700, and the wavelength was scanned (200-900 nm).
[0276] The results are shown in Figures 6 to 9 .Depend on Fig. 9 It can be seen that the lignin self-assembly exhibits anti-Stokes fluorescence.
[0277] In addition, for the obtained self-assembly (hollow spherical particles of lignin-sugar complex), a complex with gold was synthesized. An aqueous solution containing the self-assembly solution and tetrachloroauric (III) acid (special grade, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was prepared, and the reaction container was sealed after argon replacement in the reaction container. The solution was irradiated with 28kHz ultrasonic waves for 10 minutes (manufactured by Honda Electronics (AS ONE), triple-frequency ultrasonic cleaner VS-10III). The solution was filtered using a filter (manufactured by pluriSelect LifeScience, pore size 1μm), and the filtrate was analyzed using a dynamic light scattering meter (manufactured by Horiba, Ltd., SZ-100NanoparticleSize Analyzer) and an ultraviolet-visible spectrophotometer (manufactured by Shimadzu Corporation, UV-2700).
[0278] As a result, the particle size distribution of the self-assembly measured by dynamic light scattering showed that the particle size of the composite with gold (Au composite 5003, solid line) was smaller than that of the self-assembly alone (LCC4936, dotted line). The mode diameters were 143.8 nm and 113.5 nm, respectively.
[0279] in addition, Fig.17 An example of the ultraviolet visible absorption spectrum of the stirred solution is shown. The absorption visible in the range of 530-540nm can be attributed to the surface plasmon resonance absorption of gold (Creighton et al., J. Chem. Soc. Faraday Trans., Vol. 87, p. 3881, 1991). It can be seen that the gold ions are reduced by reacting with the self-assembly to generate stable gold nanoparticles.
[0280] The unreduced gold (III) ions in the reaction solution can be quantified as follows (Mizukoshi et al., Analytical Chemistry, Vol. 45, No. 4, p. 327, 1996). A predetermined amount of an aqueous solution containing a self-assembly solution and gold (III) tetrachloride is reacted for a predetermined time. A saturated aqueous solution of sodium bromide is added to the reaction solution, and the agglomerates produced by salting out are filtered and separated by centrifugation or the like. This eliminates the interference of the spectrum caused by the nanoparticles. On the other hand, the unreacted gold ions coordinate with the added bromide ions, and absorption of the gold (III) tetrabromide ions appears near 381nm. Using a pre-made calibration curve, the unreacted gold ions in the reaction solution are colorimetrically quantified. The amount of gold ions reduced and the electrons provided to the gold ions during reduction are calculated, and the amount of electrons supplied per 1 mg of the self-assembly is determined.
[0281] For example, 4 μmol of gold ions were consumed by 1.9 mg of the self-assembly. This means that 4×3 μmol of electrons were provided to the gold ions. In other words, 6.3 μmol of electrons were provided per 1 mg of the self-assembly.
[0282] Reference Test Example 4. Measurement of UV Absorption
[0283] The ultraviolet absorption properties of the lignin and lignin-hemicellulose complex used in Reference Test Example 2 were measured. Specifically, the sample was dissolved in ethanol at 0.005 w / v%, and the ultraviolet absorption spectrum of the obtained solution (transparent) was measured using a spectrophotometer (manufactured by Shimadzu Corporation, UV-2700) (optical path length 1 cm, quartz cuvette).
[0284] The results are shown in Fig.10 It is known that the lignin and lignin-hemicellulose complex obtained by the method of the present invention exhibit broad ultraviolet absorption in the wavelength regions of UV-A (320 nm to 400 nm) and UV-B (280 nm to 320 nm).
[0285] Reference Test Example 5. Preparation of Hollow Spherical Particles 1
[0286] Using the lignin used in Reference Test Example 2 as a sample, hollow spherical particles as a self-assembled body were prepared. Specifically, the process was as follows.
[0287] (1) 20 mg of a lignin sample (dry powder) was dissolved in 1.0 mL of DMSO to prepare a 2% w / v lignin solution.
[0288] (2) Add 0.1 mL of 2% w / v lignin stock solution to 0.9 mL of 80% v / v ethanol solution, and stir and mix evenly.
[0289] (3) Slowly add 3 mL of water dropwise while stirring to dilute. The dilution rate can be changed. When the organic solvent concentration is below 40%, hollow spherical particles begin to form, and a stable dispersion state is observed at 5-30%.
[0290] Alternatively, hollow spherical particles can be obtained by using the following step (4) instead of the above step (3).
[0291] (4) Slowly drop 1 mL of alcohol-water solvent while stirring. The alcohol-water solvent is a 30% ethanol solution or a 10% n-butanol solution. Then, blow gentle nitrogen gas to the surface of the solution, or gasify it by air drying, or distill under reduced pressure to remove the solvent. When the organic solvent concentration is below 40%, hollow spherical particles begin to form, and a stable dispersion state is observed at 5-30%.
[0292] The bright field image of the obtained hollow spherical particles is shown in Fig. 11-1. Large particles (particle diameter of 5 μm or more) and small particles (particle diameter of less than 5 μm) were confirmed.
[0293] In addition, the particle size and film thickness of a larger particle were measured, and the volume occupied by the inner cavity in the hollow spherical particle (inner cavity ratio) was calculated. Specifically, the fluorescence observation performed using a 100x objective lens was photographed using a Keyence integrated fluorescence microscope BZ-X810 in slice mode, and the particle size and film thickness were calculated using Keyence's analysis software based on the obtained image data. The inner cavity ratio (unit: %) is calculated by the formula: inner cavity ratio = (volume of the inner cavity part of the hollow spherical particle (excluding the membrane part) / volume of the entire hollow spherical particle) × 100. As a result, the particle size was 21.1 μm, the film thickness was 635 nm, and the inner cavity ratio was 83%.
[0294] Reference Test Example 6. Preparation of Hollow Spherical Particles 2
[0295] Using the lignin used in Reference Test Example 2 as a sample, hollow spherical particles containing a drug were prepared. The specific method was as follows.
[0296] 0.1% w / v of near-infrared fluorescent dye DiR (DiIC18 (7)) and 1.0 mL of 80% ethanol solution were mixed with stirring in 0.2% w / v lignin solution (in 80% ethanol). Water or alcohol-water solvent was added dropwise while stirring and mixed, and the organic solvent concentration was reduced in the same manner as in Reference Test Example 5 to form hollow spherical particles.
[0297] An image observed using a fluorescence microscope is shown in Fig. 12-1. Particles showing near-infrared fluorescence derived from the enclosed pigment were observed.
[0298] Reference Test Example 7. Preparation of Hollow Spherical Particles
[0299] Hollow spherical particles were prepared using the lignin used in Reference Test Example 2 as a sample. The specific method was as follows.
[0300] Prepare a 2.5wt% solution (30% ethanol) of lignin (from eucalyptus), stir to form a uniform solution, and use it as the stock solution. While stirring, slowly add 200μL of 50% organic solvent (ethanol, 1-propanol, allyl alcohol, 2-propanol or 1-butanol) to 100μL of the stock solution to make a uniform solution. While stirring, slowly add 1.7mL of water to make a uniform solution. For the resulting liquid (final concentration 0.125wt% organic solvent 5% (containing 0.015% ethanol)), use DLS to measure nanoparticles. The DLS measurement uses a multi-specimen nanoparticle size measurement system, adds 2mL of sample to a glass disposable sample cell, and uses dynamic light scattering to measure the particle size. The measurement is performed 3 times each, and the average value is calculated. The measurement temperature is 25°C, and the solvent refractive index is 1.33.
[0301] The results are shown in Table 9.
[0302] [Table 9]
[0303]
[0304] In addition, the same test as above was carried out using lignin from other tree species (Japanese pine, Japanese cypress, Japanese cedar, beech, bamboo) (lignin obtained by the same method as Reference Test Example 2), and the same results were obtained for the average particle size and polydispersity index.
[0305] Example 1. Preparation of hollow spherical particles
[0306] Hollow spherical particles were prepared using the lignin or lignin-hemicellulose composite used in Reference Test Example 2 as a sample. Specifically, the process was as follows.
[0307] DMSO was added to the lignin-sugar complex or lignin powder to a concentration of 10 w / v%, and the mixture was uniformly dissolved by ultrasonic treatment. In addition, an ethanol / water solution was added as a poor solvent in a direction of gradually decreasing the organic solvent concentration, and the mixture was stirred until the final organic solvent concentration was 30%.
[0308] The obtained hollow spherical particles were measured for particle size and Zeta potential using the resistive nanopulse method (qNANO). The size distribution, concentration and Zeta charge of the nanoparticles were measured using the resistive nanopulse method (qNANO) nanoparticle multifunctional analyzer (manufactured by Izon Science, MEIWAFOSIS CO., LTD.) using the principle of TRPS. 35 μL of the particle solution was analyzed using NP200 and NP400 Nanopore under 46-47 mm stretching conditions according to the manufacturer's instructions.
[0309] The particle size of the hollow spherical particles of lignin-hemicellulose composite is smaller than the particle size of the hollow spherical particles of lignin obtained under the same conditions. The same test was carried out by changing the source tree species of the sample and the same results were obtained. The results are shown in Table 10.
[0310] [Table 10]
[0311] Sample name Average particle size [nm] Mode particle size [nm] Lignin capsules from eucalyptus 404 278 Lignin polysaccharide complex capsules from eucalyptus 283 246 Lignin capsules from Cryptomeria fortunei 362 301 Lignin polysaccharide complex capsule from Cryptomeria fortunei 285 247 Lignin capsules from red pine 380 297 Lignin polysaccharide complex capsules from red pine 286 263
[0312] In addition, the results of zeta potential measurement revealed that the lignin-hemicellulose composite hollow spherical particles were cationic nanoparticles having a high positive zeta potential of 40 to 60 mV.
[0313] The surface charge of the lignin-sugar complex capsule was measured using a resistive nano-pulse method (qNANO) nanoparticle multifunctional analyzer (manufactured by Izon Science, MEIWAFOSIS CO., LTD.).
[0314] [Table 11]
[0315] Sample name Average particle size (nm) Mode particle size (nm) Average potential (mV) Mode potential (mV) Eucalyptus LP 339 320 42.3 46.3 Eucalyptus LHP 300 276 39.1 44
[0316] Table 11 shows the particle size and zeta potential measurement results of eucalyptus-derived lignin capsules (LP) and eucalyptus-derived lignin-sugar complex capsules (LHP).
[0317] in addition, Fig.15 The particle size and zeta potential distribution of eucalyptus lignin capsules (LP, top) and eucalyptus lignin-sugar complex capsules (LHP, bottom) are shown. The particle size and zeta potential of each particle were obtained using the resistive nanopulse method (qNANO) and plotted.
[0318] In addition, a scanning microscope (SEM) image was obtained for the obtained hollow spherical particles. 0.2 mL of the solution containing the hollow spherical particles was pretreated using a nano-percolator (manufactured by JEOL Ltd.), the hollow spherical particles remaining on the film were treated with a conductive film using an osmium coating device (manufactured by MEIWAFOSIS CO., LTD.), and observed using a field emission scanning electron microscope: S-4800 manufactured by Hitachi High-Technologies.
[0319] Scanning microscope (SEM) images are shown in Figure 11-2. Lignin capsules with a particle size of 100nm to 600nm and lignin-sugar complex capsules with a particle size of 20nm to 200nm were confirmed. The SEM photographs show that the hollow spherical particles do not break even in a vacuum and can maintain their shape, which indicates the stability of the particle structure. Vesicle structures derived from natural molecules such as liposomes and exosomes are difficult to maintain their shape in normal SEM observations after a vacuum drying process, so it can be said that the structural stability deserves attention.
[0320] Lignin-sugar complex capsules have the ability to encapsulate highly hydrophilic drugs due to their characteristics as amphiphilic polymers. In fact, by the same test as Reference Test Example 6, nucleic acid staining fluorescent pigment DAPI [4,6-diamidino-2-phenylindole dihydrochloride, 4,6-Diamidino-2-phenylindole, dihydrochloride] (manufactured by Dojin Chemical Research Institute, CAS RN: 28718-90-3), chlorophyll as a pigment (manufactured by Tokyo Chemical Industry, CAS RN: 1406-65-1), and iron porphyrin complex hemin (manufactured by Tokyo Chemical Industry, CAS RN: 16009-13-5) as a metal complex were encapsulated. After the prepared capsules were separated from low molecular weight components by dialysis, the absorption of the pigment and the absorption of the Soret band and Q band regions in the UV-vis spectrum were confirmed, and the inclusion of the drug was confirmed by microscopic observation (bright field, fluorescence). As nucleic acid DNA, VIOLAMO DNA Ladder Markers (VIO-1kb manufactured by AS ONE Corporation) were encapsulated, and as protein, PrecisionPlus Protein (#1610377 manufactured by Biorad) was encapsulated. DNA was used after being pre-bound to SYBR Green fluorescent dye. In the same manner, the inclusion of the drug was confirmed by UV-vis spectroscopy and fluorescence microscopy.
[0321] FIG12-2 shows fluorescence microscopy images (Ex 360nm, Em 460nm), bright field microscopy images, and electron microscopy images of lignin-sugar complex capsules encapsulating DAPI.
[0322] Fluorescence and bright field microscopy images were taken using an integrated fluorescence microscope (BZ-X810 manufactured by Keyence Corporation). 0.2 mL of the solution containing the DAPI-encapsulated lignin-sugar complex was pretreated using a nanofiltration device (manufactured by JEOL Ltd.), and the hollow spherical particles remaining on the film were treated with a conductive film using an osmium coating device (manufactured by MEIWAFOSIS CO., LTD.), and observed using a scanning electron microscope SEM (VE-9800 manufactured by Keyence Corporation). The accelerating voltage was set to 8 kV.
[0323] The lignin-sugar complex capsule can show long-wavelength fluorescence. A representative example of the 3D fluorescence spectrum obtained by the same operation as in Reference Test Example 3 is shown in Fig.16 .
[0324] Example 2. Preparation of hollow spherical particles
[0325] Hollow spherical particles were prepared in the same manner as in Example 1, using the lignin or lignin-hemicellulose composite used in Reference Test Example 2 as a sample.
[0326] The average particle size of the obtained hollow spherical particles was measured in the same manner as in Example 1.
[0327] The stability of the lignin-hemicellulose composite hollow spherical particles and the lignin hollow spherical particles obtained under the same conditions was compared and evaluated under the conditions of solute concentration (0.5 w / v%), solvent: 30 v / v% ethanol / water, and room temperature.
[0328] In addition, the fine particle solution was heated and stirred, and the average particle diameter after 0.5 hours had passed was measured.
[0329] The stability of particle size and temperature stability are shown in Fig.13 and Fig.14 The lignin-hemicellulose composite particles showed excellent properties in terms of dispersion maintenance, structural stability, and temperature stability over time. Specifically, as for dispersion maintenance and structural stability, the change rate of the number average particle size and the mode average particle size within 6 weeks was within ±13%, and as for temperature stability, the change rate of the average particle size within the range of 10°C-70°C was within ±5%.
[0330] Example 3. Experiment on introducing protein into lignin-sugar complex capsule from eucalyptus
[0331] Lignin-sugar complex capsules can be made under mild conditions, and therefore have the ability to encapsulate proteins and nucleic acids, which are biopolymers. Polysaccharides have high biocompatibility and are expected to be used as DDS.
[0332] Normally, the surface charge of liposomes or PEG-modified nanocarriers is negative, so the efficiency of uptake into cells is low. Lignin-sugar complex capsules show a high positive surface charge in water (weakly acidic) (Zeta potential measurement results, mode average: +44mV, particle size 276nm). In alkaline conditions (50mM PBS, pH11), they show a negative surface charge (Zeta potential measurement results, mode average: -21mV, particle size 302nm). Such characteristics have an additional function as a cationic drug carrier (DDS) with high cell uptake efficiency. In addition, it is beneficial to the introduction effect of drugs in tumor tissues in an acidic environment and the retention of nanocarriers. In addition, as pH responsiveness, it has the function of a pH-responsive nanocarrier that can switch from positive charge to negative charge without changing the particle size.
[0333] Example 4. Sustained release of eucalyptus lignin-sugar complex capsules using saccharolytic enzymes
[0334] Bovine serum albumin (Novagen) was used as a protein. Albumin was fluorescently labeled at 100 μg / ml. Fluorescent labeling was performed using WSE-7010EzLabel FluoroNeo (ATTO Corporation). 10 μL of albumin solution (50 μg / ml, 0.5 μg) was added to 200 μL of lignin-sugar complex (0.5 w / v, 35% v / v ethanol solution), and after being encapsulated in the lignin-sugar capsule, it was observed through a filter using a Keyence integrated fluorescence microscope BZ-X810. As a fluorescence microscope image (with a fluorescence filter for GFP installed), the inclusion of the fluorescently labeled protein was observed.
[0335] Next, hemicellulase (Amano 90, Amano Enzyme Inc.), a polysaccharide degrading enzyme, was added to a final concentration of 1 mg / mL and cultured at 50° C. for 90 min. It was observed that the fluorescence was no longer clearly visible due to the enzyme treatment, and the labeled protein leaked out of the lignin-sugar capsule, achieving sustained release.
[0336] Example 5. Analysis of Hollow Spherical Particles
[0337] 5-1. Methods
[0338] 5-1-1. Production of hollow spherical particles
[0339] Eucalyptus lignin (PA1%AA, MW50, ACTN) and eucalyptus LCC lignin (PA1%AA, MW50→140, ACTN) were used. First, for each lignin stock solution 10w / v% dissolved in DMSO, it was diluted with DMSO to prepare lignin stock solutions of different concentrations. Five concentrations of 1.0w / v%, 2.5w / v%, 5.0w / v%, 7.5w / v%, and 10w / v% were prepared. 10μL of each concentration of lignin solution was prepared in a 1.5mL tube. The particle size was evaluated using the resistive nanopulse method (qNANO) (NP400). The measurement was performed under the conditions of Pressure 5 and Tension 47.01cm. In addition, the sample was diluted with PBS buffer to which a surfactant was added. The dilution ratio is shown in the table. In addition, 35μL of sample diluent was added during the measurement.
[0340] 5-1-2. Study on temperature conditions during assembly
[0341] Confirm how the temperature conditions affect the particle size and particle concentration of the particles when the particles are assembled by stirring and rotating reaction with an organic solvent. The samples used eucalyptus lignin (PA1% AA, MW50, ACTN) and eucalyptus LCC lignin (PA1% AA, MW50→140, ACTN). 10μL of 10w / v% lignin stock solution dissolved in DMOS was injected into each 1.5mL tube. When mixed with lignin / DMSO solution, 50μL of EtOH of each concentration was used, but since the rotation reaction was carried out under high temperature conditions, 60μL was prepared for each, taking into account the volatilization of the solvent. The temperature conditions at this time were carried out under five different conditions of 10°C, 25°C, 40°C, 55°C, and 70°C. In addition, before the rotation reaction, the lignin stock solution and each EtOH solution were temperature-adjusted using an Eppendorf Thermo mixer to reach the same temperature as during the rotation reaction. The produced microparticles were evaluated by the resistive nanopulse method (qNANO) to compare the particle size and concentration.
[0342] 5-1-3. Effect of stirring speed on particle size when adding organic solvent
[0343] The effect of the stirring speed of the solution on the particle size of the particles was studied. Eucalyptus lignin (PA1%AA, MW50, ACTN) was used as the sample. At this time, the five conditions of the rotation speed were 300rpm, 600rpm, 900rpm, 1200rpm, and 1500rpm. The particle size of the lignin particles was measured using the resistance nano-pulse method (qNANO).
[0344] Furthermore, the microparticles prepared at 300 rpm were reacted at 1500 rpm to examine the change in particle size. 180 μL of the sample prepared at 300 rpm was mixed at 25° C. and 1500 rpm for 5 minutes (300 to 1500 rpm sample).
[0345] Next, eucalyptus LCC lignin (PA1%AA, MW50, ACTN) was used to evaluate the particle size of microparticles affected by the rotation speed. The rotation speed was 300 rpm, 500 rpm, 700 rpm, and 900 rpm. The particle size of lignin microparticles was measured using the resistance nano-pulse method (qNANO).
[0346] 5-1-4. Comparison of the effect of centrifugal direction on particle size
[0347] The equipment and rotation direction when mixing the lignin solution with the organic solvent were studied. The effects of longitudinal rotation, transverse rotation, and the differences in the equipment used on the particle size of the lignin microparticles were studied. A 10w / v% lignin / DMSO solution and 80v / v%, 40v / v%, and 20v / v% ethanol aqueous solutions were prepared as in Experimental Method 1-1. When mixing the lignin solution with the ethanol aqueous solution, 50μL was added in stages starting from the high concentration of ethanol aqueous solution, and the centrifugation was repeated. During centrifugation, an Eppendorf constant temperature mixer was used to centrifuge at 1000rpm in the X-axis direction, and a Lab Serb was used to stir at 1000rpm in the X-axis and Y-axis directions. The obtained lignin microparticles were measured using the resistance nanopulse method (qNANO) of NP400 to determine the particle size.
[0348] 5-1-5. Particle size evaluation under buffer conditions of different pH values
[0349] Confirm whether the particle size of the particles and the ease of particle generation differ due to the type of buffer added when making lignin particles. Eucalyptus lignin (PA1%AA, MW50, ACTN) and eucalyptus LCC lignin (PA1%AA, MW50→140, ACTN) were used as samples. The added ethanol aqueous solution was prepared in three types: 80v / v%, 40v / v%, and 20v / v%, and the number of each sample was × 50μL. At this time, ethanol was diluted with each buffer. The buffer was prepared by diluting 1M MOPS / NaOH buffer (pH6.4), 1M PIPES / NaOH buffer (pH6.2), and 1M HEPES / NaOH (pH 8.2) to a final concentration of 50mM. The particle size of lignin particles was evaluated using the resistance nanopulse method (qNANO) of NP400. In addition, the particle size evaluation of LCC lignin particles was evaluated based on the resistance nanopulse method (qNANO) using NP200.
[0350] 5-1-6. Study of added organic solvents
[0351] Compare the effects of the organic solvents used in the assembly of lignin on the particle size of the microparticles and the ease with which lignin is assembled. The samples used eucalyptus lignin (PA1%AA, MW50, ACTN) and eucalyptus LCC lignin (PA1%AA, MW50→140, ACTN). The assembly of lignin was carried out under the same conditions as experimental method 1-1. On the other hand, the added organic solvents used were methanol, ethanol, 1-propanol, and 1-butanol diluted with pure water to 80v / v%, 40v / v%, and 20v / v%.
[0352] The particle size evaluation and concentration difference were measured using NP400 Nanopore using the resistive nanopulse method (qNANO).
[0353] 5-1-7. Assembly using lignin from different tree species
[0354] In addition to eucalyptus, which is a broad-leaved tree, coniferous trees such as cedar and red pine were used to study whether lignin microparticles can be produced. The seven tree species (resins) used were eucalyptus lignin (PA1%AA, MW50, ACTN), eucalyptus LCC lignin (PA1%AA, MW50→140, ACTN), cedar lignin (H2O2 3.2%+AA, MW50, 80DOX), cedar LCC lignin (H2O23.2%+AA, MW50→140, 80DOX), red pine (H2O2 3.2%+AA, MW50, ACTN), red pine LCC lignin (H2O2 3.2%+AA, MW50→140, ACTN), and bamboo lignin (MS130-5). The particles were micronized and the particle size was evaluated using NP400 using the resistive nano-pulse method (qNANO) measurement.
[0355] [Table 12]
[0356] <Dilution ratio for measuring lignin fine particles using the resistive nanopulse method (qNANO)>
[0357] species Dilution ratio (times) Eucalyptus wood (PA1AA, MW50, ACTN) 20 Eucalyptus LCC lignin (PA1AA, MW50→140, ACTN) 10 <![CDATA[Cryptomeria japonica lignin (H2O2 3.2% + AA, MW50, 80DOX)]]> 1.1 <![CDATA[Cryptomeria fortunei LCC lignin (H2O2 3.2% + AA, MW 50 → 140, 80 DOX)]]> 5.0 <![CDATA[Pinus densiflora (H2O2 3.2% + AA, MW50, ACTN)]]> 1.2 <![CDATA[Pinus densiflora LCC lignin (H2O2 3.2% + AA, MW 50 → 140, ACTN)]]> 5.0 Bamboo lignin (MS130-5) 10
[0358] 5-1-8. Particle evaluation using the resistance nanopulse method (resistance nanopulse method (qNANO))
[0359] In both cases of NP200 and NP400, the stretching condition of Nanopore is adjusted to 47 mm. In addition, the voltage is adjusted so that the current value reaches about 120 nA when the buffer is added. First, the sample is measured after calibration. The calibration sample uses an average particle size of 350 nm, a mode particle size of 330 nm, and a concentration of 8.4E+11 particles / mL. Dilute 500 times with PBS buffer to which a surfactant is added, and load 35 μL for measurement. Then perform the sample measurement. The sample is diluted with PBS buffer, and 35 μL is used for measurement. The measurement time is within 10 minutes. Click when the current value is unstable.
[0360] 5-1-9. Particle size evaluation using dynamic light scattering
[0361] Particle size evaluation was performed using SZ-100Nanoparticle Size Analyzer (HORIBA). A 4-sided transparent quartz cuvette was used for measurement. When preparing the sample, the lignin particle sample was diluted 100 times with pure water and 2 mL was prepared. The measurement time was in automatic mode, and the peak trend was measured with polydispersity and standard peak. The measurement was performed more than 3 times, and the average value was calculated to evaluate the particle size.
[0362] 5-1-10. Particle size evaluation using interference microscopy
[0363] The particle size of the microparticles was evaluated using a nanoparticle imaging analyzer VIDEO DROP (MEIWAFOSIS CO., LTD.). The prepared lignin microparticles were diluted 100 times with pure water for measurement. During the measurement, the presence or absence of aggregates was confirmed by the monitor while the measurement was performed. 8 μL of the diluent was used for the measurement, and the measurement was performed until the sample count reached 300 or more.
[0364] 5-2. Results
[0365] 5-2-1. Particle size distribution analysis
[0366] The analysis results of the particle size and the time it takes to pass through the hole for each particle are shown in Fig.18 The distribution of the plotted points on the diagonal line indicates that the sphericity (symmetry) of the particles is high.
[0367] 5-2-2. Observation of nanoparticles using a microscope
[0368] Ethanol / water solution was slowly added to eucalyptus lignin (PA1% AA, MW50, ACTN) to create a poor solvent condition overall, and lignin microparticles were produced. The shape of the nanoparticles was observed using a scanning probe microscope SPM-Nanoa (Shimadzu Corporation), and the physical properties were evaluated. According to the results of SPM, it was confirmed that microparticles with a size of less than 100 nm were produced (Table 13). Also, it was confirmed that even for nanoparticles, the particle shape was spherical ( Fig.19 ). According to the analysis results of the physical properties of the nanoparticles, it was confirmed that the lignin microparticles had a lower affinity for the probe tip compared to mica, but were relatively soft ( Fig.21 ).
[0369] [Table 13]
[0370] <SPM Nanoparticle 3D Stereo Height Analysis Results>
[0371]
[0372] [Table 14]
[0373] <SPM Nanoparticle 3D Tilt Analysis Results>
[0374]
[0375] Next, 3D true surface vision microscopy was used to observe LCC lignin nanoparticles made from eucalyptus LCC lignin (PA1% AA, MW50 → 140, ACTN). After drying the produced microparticles with a nano filter, subsequent osmium coating was performed, and observation was carried out using 3D true surface vision microscopy. According to the experimental results, spherical microparticles were observed ( Fig. 22 ).
[0376] The particle size of nanoscale LCC lignin microparticles made from eucalyptus LCC lignin (PA1% AA, MW50 → 140, ACTN) was evaluated using an interference microscope and DLS. According to the experimental results, the median particle size obtained using the interference microscope was 98 nm, the mode particle size was 105 nm, and the above particle sizes obtained using DLS were 90.7 nm and 85.0 nm, respectively (Table 15). According to the experimental results of the interference microscope, it was also confirmed that granular nanoparticles were generated ( Fig.23 ).
[0377] [Table 15]
[0378] <Particle Size Evaluation of LCC Nanoparticles>
[0379] Parsing Methods Median particle size (nm) Mode particle size (nm) Interference Microscopy 98 105 Dynamic light scattering 90.7 85.0
[0380] 5-2-3. Evaluation of dispersibility of lignin particles
[0381] 5-2-3-1. Zeta potential measurement using the resistive nanopulse method (qNANO) Microparticle samples were prepared from eucalyptus lignin (PA1%AA, MW50, ACTN) and eucalyptus LCC lignin (PA1%AA, MW50→140, ACTN) using phosphate buffer from pH 3 to pH 11 in increments of pH 2 each time. The Zeta potential of the microparticles was measured by the resistive nanopulse method (qNANO) of NP400. First, calibration was performed. The calibration measurement concentrations were V1P 2, V1P1, V2P1, V3P1 in sequence to confirm that accurate calibration could be carried out. Also, the calibration particles did not block the pores, and the microparticle count showed a good linear ratio with respect to the measurement time. First, the particle size of the calibration particles was measured. As a result of the measurement, the median particle size was 330 nm, and it was confirmed that accurate calibration measurement could be carried out.
[0382] According to the Zeta potential measurement results of the lignin microparticles, the average paired value was a positive potential of 30.5 mV under acidic conditions of pH 3, while it was a negative potential of -26.6 mV under alkaline conditions of pH 11 (Table 16). It was confirmed that under neutral conditions, microparticles with a particle size greater than 250 nm showed a positive Zeta potential, and microparticles below 300 nm were both negatively and positively charged ( Fig.28 ). From this, it can be considered that there may be a correlation between the Zeta potential and the particle size.
[0383] In the LCC lignin microparticles, a large number of microparticles that were positively charged under any pH conditions were visible (Table 17). Under the condition of pH 7, similar to the lignin microparticles without polysaccharides, microparticles that were both negatively and positively charged were confirmed when the particle size was below 300 nm ( Fig.30 ). From this, it can be seen that as the pH moves towards the alkaline side, the plotted points tend to expand vertically ( Fig.34 Fig.35 ).
[0384] [Table 16]
[0385] <Measurement Results of Particle Size and Zeta Potential of Lignin Microparticles at Each pH>[
[0386]
[0387] [Table 17]
[0388] <Measurement Results of Particle Size and Zeta Potential of LCC Lignin Microparticles at Each pH>[
[0389]
[0390] 5-2-3-2. Zeta potential measurement using DLS
[0391] Microparticle samples were prepared from eucalyptus lignin (PA 1% AA, MW50, ACTN) and eucalyptus LCC lignin (PA 1% AA, MW50→140, ACTN) using phosphate buffer from pH 1 to pH 13 in increments of pH 2, and the zeta potential of the microparticles was measured by DLS.
[0392] According to the experimental results, in lignin particles, as the pH increases from acidic to alkaline, the average Zeta potential presents a more negative value (Table 18). Moreover, under the conditions of pH 1 and 3, the mode Zeta potential is a positive value of 1.67mV and 1.48mV, respectively. Moreover, the peaks of the Zeta potential observed from neutral conditions are multi-peaks rather than single peaks. On the other hand, in LCC lignin particles, under acidic conditions of pH 1, the average Zeta potential is a positive value of 2.81mV, but under alkaline conditions of pH 3, it is negatively charged. In particular, at pH 9, the average Zeta potential is -75.6mV, showing a Zeta potential with an absolute value greater than that of lignin particles without polysaccharides (Table 19).
[0393] [Table 18]
[0394] <Results of Zeta Potential Measurement of Lignin Fine Particles Using DLS>
[0395]
[0396] [Table 19]
[0397] <Results of Zeta Potential Measurement of LCC Lignin Fine Particles Using DLS>
[0398]
[0399] According to the results of Zeta potential measurement obtained by the resistance nanopulse method (qNANO), the smaller the particle size, the easier it is to be negatively charged. It can be considered that there is a correlation between particle size and Zeta potential ( Fig.33 ). Since the resolution range of particle size is different when using the resistance nanopulse method (qNANO) and the Zeta potential, the potential is different. The particle size of LCC lignin particles at pH 7 was measured by DLS. As a result, the median particle size was 113nm and the mode particle size was 78.7nm, which was 239nm ( Fig.33 ), nanometer-scale particles were observed.
[0400] 5-2-4. Evaluation of particle size maintenance of lignin particles
[0401] Determine the rate of change of the particle size of the lignin particles with respect to the elapsed time. Lignin particles were made using species of eucalyptus lignin (PA1%AA, MW50, ACTN) and eucalyptus LCC lignin (PA1%AA, MW50→140, ACTN), and the rate of change of the average particle size and the mode particle size over 6 weeks was measured. The particle size of the lignin particles in week 0 was set to 100%, and the experimental results showed the extent to which the particle size was maintained after the second week. In the LCC lignin particles, the change in the average particle size was within 15% even after 6 weeks (Table 20). In addition, in the lignin particles and LCC lignin particles, the maintenance of the mode particle size after 6 weeks was almost 100% (Table 21).
[0402] [Table 20]
[0403] <Average Particle Size and Shape Retention over Time>
[0404] Tree species / Time elapsed (weeks) 1 2 3 4 5 6 Lignin particles (%) 74 101 68.2 69.2 67.6 62.8 LCC lignin particles (%) 86.5 95.1 77.9 88 85.3 86.8
[0405] [Table 21]
[0406] <Maintenance of the mode particle size over time>
[0407] Tree species / Time elapsed (weeks) 1 2 3 4 5 6 Lignin particles (%) 97.5 95.3 87.5 106 96.9 102 LCC lignin particles (%) 97.6 94.1 87.1 108 89.9 99.7
[0408] [Table 22]
[0409] <Measurement Results of Average Particle Size over Time>
[0410]
[0411] [Table 23]
[0412] <Measurement results of mode particle size over time>
[0413]
[0414] Using eucalyptus LCC lignin (PA1% AA, MW50→140, ACTN), microparticles were prepared in which eosin molecules were compounded as a drug model compound during lignin assembly. The fluorescence excitation wavelengths of the prepared eosin-complex microparticles and microparticles without eosin were measured, and the shift of the peak wavelength was confirmed ( Fig.36 , Fig.37 ). The peak fluorescence wavelength of the microparticles without eosin is 428 nm and the excitation wavelength is 310 nm, while the peak fluorescence wavelength of the microparticles with eosin is 456 nm and the excitation wavelength is 346 nm.
[0415] 5-2-5. Pharmaceutical Combination Test
[0416] Eucalyptus LCC lignin (PA1% AA, MW50→140, ACTN) was combined with diethyl sebacate used in pharmaceuticals and cosmetics to produce microparticles. Diethyl sebacate is commonly used to promote the penetration effect of fat-soluble substances into the stratum corneum or hair and is used as an emulsifier. The particle size of the prepared microparticles was measured using the resistive nanopulse method (qNANO) with NP400 and DLS. Each measurement was performed twice, and the average values are shown in Table 24. According to the results, it was confirmed that a large number of microparticles around 300 nm to 400 nm were generated. And the fluorescence excitation spectrum was measured. According to the experimental results, compared with the results of the fluorescence excitation spectrum of the microparticles made of ethanol aqueous solution ( Fig.36 ), peaks appeared on the long-wavelength side for both fluorescence and excitation wavelengths. Also, two peaks were confirmed at a fluorescence wavelength of 450 nm and excitation wavelengths of 279 nm and 370 nm ( Fig.39 ).
[0417] [Table 24]
[0418] <Particle Size Evaluation of Diethyl Sebacate Composite Microparticles>
[0419] Determination method Median particle size (nm) Mode particle size (nm) qNano 373 304 DLS 462 459
[0420] 5-2-6. Evaluation of the effect of temperature change on particles
[0421] 5-2-6-1. Particle size evaluation for temperature changes
[0422] The change rate of the particle size of lignin microparticles caused by continuous temperature changes was measured. Lignin microparticles were made using the tree species of eucalyptus lignin (PA1% AA, MW50, ACTN) and eucalyptus LCC lignin (PA1% AA, MW50→140, ACTN), and the temperature was increased stepwise by 10 °C each time, and the change rate of the particle size was measured by DLS. According to the experimental results, after the microparticles were made, even when the temperature was increased, the particle size of the lignin microparticles did not change significantly (Table 25). For the LCC lignin microparticles, when the temperature was increased from 20 °C to 60 °C, the average particle size value decreased by about 10 nm (Table 26).
[0423] [Table 25]
[0424] <Particle Size Evaluation of Lignin Microparticles with Temperature Changes>
[0425] Temperature(℃) 10 20 30 40 50 60 Median particle size (nm) 145 145 152 152 148 135 Mode particle size (nm) 134 128 150 150 136 126
[0426] [Table 26]
[0427] <Particle Size Evaluation of LCC Lignin Microparticles with Temperature Changes>
[0428] Temperature(℃) 10 20 30 40 50 60 Median particle size (nm) 70.2 67.8 63.3 63.7 56.3 57.3 Mode particle size (nm) 65.1 64.6 62.3 61.8 56.3 57.2
[0429] 5-2-6-2. Evaluation of Zeta potential caused by changes
[0430] Measure the rate of change of the Zeta potential of lignin microparticles caused by continuous temperature changes. Lignin microparticles were prepared using eucalyptus lignin (PA1% AA, MW50, ACTN), and the temperature was increased stepwise by 10 °C each time, and the Zeta potential was measured continuously. According to the experimental results, compared with the low-temperature conditions, the closer to room temperature, the greater the value of the Zeta potential (Table 27).
[0431] [Table 27]
[0432] <Evaluation of the Zeta potential of LCC nanoparticles with temperature changes>
[0433] Temperature(>) 10 20 30 40 50 60 Zeta potential (mV) -7.20 -12.4 -15.1 -10.4 -15.6 -11.9
[0434] Experimental Example X. Preparation and Analysis of Water-in-Oil (W / O) and Oil-in-Water (O / W) Self-Assemblies
[0435] Preparation and analysis of water-in-oil (W / O) type and oil-in-water (O / W) type self-assemblies of lignin-sugar complexes
[0436] The lignin-sugar complex separated by the A-APA method (microwave treatment at 140 °C for 10 minutes, acetic acid-peracetic acid 1% or acetic acid-0.2 M hydrogen peroxide conditions) was further dispersed in an aqueous solution, and the insoluble part and the soluble part were separated respectively. The insoluble part was used as the raw material for the O / W type, and the soluble part was used as the raw material for the W / O type. The results of separation using an aqueous solution containing 10% acetic acid are shown in Table 28. Regarding the sugar unit content rate (%) relative to 100 aromatic ring units, the ratio of the sugar unit (calculated based on the integral value of the signal peak related to the anomeric carbon) to the aromatic ring unit was calculated as a percentage according to the HSQC NMR spectrum.
[0437] [Table 28]
[0438]
[0439] Prepare a 10 wt% aqueous solution of lignin-polysaccharide complex (W / O type), and add 200 μL of 1-butanol (FUJIFILM Wako Pure Chemical Corporation, special grade) as a separation solvent to 10 μL of this aqueous solution. While irradiating ultrasonic waves with a frequency of 28 kHz in the cleaning tank of an ultrasonic cleaner, the addition was carried out to obtain a self-assembly.
[0440] For the oil-in-water (O / W) type, it was prepared in the same manner as the other described parts.
[0441] The structure of the self-assembly was measured using a fluorescence microscope (integrated fluorescence microscope BZ-X810, manufactured by Keyence Corporation). Photographs of the hollow spherical particles of the water-in-oil (W / O) type lignin-sugar complex from Pinus densiflora are shown in Fig.40 。
Claims
1. A hollow spherical particle, which is a self-assembled body of a lignin-sugar complex, wherein the hollow spherical particle is characterized in that: The lignin-sugar complex is a lignin-sugar complex having at least one type of bond selected from the group consisting of an α-ether bond, an α-ester bond, and a γ-ester bond between lignin and a polysaccharide.
2. The hollow spherical particle according to claim 1, characterized in that: The composition ratio of the polysaccharide to the lignin in the lignin-sugar complex is 0.1 to 10 in terms of the ratio obtained by dividing the number of monomer units of the polysaccharide by the number of monomer units of the lignin.
3. The hollow spherical particle according to claim 1, characterized in that: The molecular weight Mw of the lignin-sugar complex is 2,000 to 10,000, and the polydispersity coefficient Mw / Mn is 2.5 or less.
4. The hollow spherical particle according to claim 1, characterized in that: It is a collection of hollow spherical particles composed of a lignin sugar complex having an average particle diameter of 200 nm or more, and has a positive average zeta potential at pH = 7 and room temperature.
5. The hollow spherical particle according to claim 1, characterized in that: It is a collection of hollow spherical particles composed of lignin sugar complexes with an average particle size of less than 200 nm, and the average Zeta potential at pH = 7 and room temperature is negative.
6. The hollow spherical particle according to claim 1, characterized in that: The number average particle size is 1 μm or less.
7. The hollow spherical particle according to claim 1, characterized in that: Contains active ingredients.
8. The hollow spherical particle according to claim 7, characterized in that: The active ingredient is at least one selected from pigments, pesticides, fertilizers, medicines, cosmetic ingredients, fragrances, fluorescent agents, coatings, proteins, antibodies, nucleic acids, vaccines, lipids, hormones, sugars, glycosides, surfactants, adhesives, vitamins, coenzymes, minerals, cells, organelles, low molecular weight compounds, high molecular weight compounds, metal complexes, liposomes and hydrogels.
9. The hollow spherical particle according to claim 1, characterized in that: Displays long-wavelength fluorescence above 450nm.
10. A drug delivery or introduction agent, characterized in that: Contains the hollow spherical particles according to any one of claims 1 to 9.
11. The drug delivery or introduction agent according to claim 10, characterized in that: The agent is a nucleic acid.
12. An ultraviolet absorber, characterized in that: Contains the hollow spherical particles according to any one of claims 1 to 9.
13. A light resistance imparting agent, characterized in that Contains the hollow spherical particles according to any one of claims 1 to 9.
14. An anti-Stokes fluorescent agent, characterized in that Contains the hollow spherical particles according to any one of claims 1 to 9.